Solidified body containing biological sample

By using a water-soluble polysaccharide matrix without cell penetrating chemical cryopreservation in cell cryopreservation, the problem of cell damage during cryopreservation is solved, high survival rate and functional maintenance of cells are achieved, and the risk of contamination is reduced.

JP2025061934AInactive Publication Date: 2025-04-11IBIDEN CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025012975
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-02-15
Filing Date
2025-01-29
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as damage to cell membrane and cell structure, cell protein denaturation, and commonly used chemical cryoprotective agents such as DMSO are cytotoxic, affecting cell survival and functional maintenance.

Method used

A solidified body that does not contain a cell-penetrating chemical cryoprotectant is used to protect biological samples, especially cells, by using a water-soluble polysaccharide or a salt thereof as a matrix during the freezing process.

Benefits of technology

High survival rate and functional maintenance of cells are achieved, cytotoxicity of chemical cryoprotectants is avoided, and does not contain serum or serum derivatives, reducing the risk of bacterial and viral contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061934000004
    Figure 2025061934000004
  • Figure 2025061934000005
    Figure 2025061934000005
  • Figure 2025061934000006
    Figure 2025061934000006
Patent Text Reader

Abstract

To provide solidified bodies containing a biological sample with high cell viability, and to provide production method thereof.SOLUTION: Provided is a solidified body containing a matrix and biological sample containing an aqueous solvent and a water-soluble polymer or salt thereof, the biological sample having an orthogonal projection area reduced by less than 1 and 1 / 3.5 or more compared to that in the culture medium before solidification, the difference between the brightness in the Munsell color system of the region occupied by the biological sample and the brightness in the Munsell color system of the region occupied by the matrix being 3 or less, when viewed from the light emitting side when visible light is transmitted, and no endothermic peak on the DSC curve being confirmed, or the temperature at which the endothermic peak is confirmed exceeding -1.4°C and is 1.1°C or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solidified body comprising a matrix and a biological sample or a method for producing a solidified body. [Background technology]

[0002] With the recent dramatic development of regenerative medicine research, regenerative medicine such as cell therapy is being actively conducted not only in humans but also in the veterinary field. Bone marrow-derived mesenchymal stem cells and adipose-derived mesenchymal stem cells collected from living organisms are mass-produced after collection and used in the above-mentioned regenerative medicine and regenerative medicine research. In this case, it is common to freeze and store the surplus cells and use them as appropriate. There is also an increasing demand for a stable supply of such cells.

[0003] It is known that in the mechanism of cell cryopreservation, when ice crystals grow inside cells during the freezing and / or thawing process, the cell membrane and intracellular structures are damaged, and the cellular proteins are denatured, resulting in fatal damage to the cells. Therefore, when cryopreserving cells, it is important to prevent intracellular freezing. Usually, for cell cryopreservation, low molecular weight compounds such as methyl sulfoxide (DMSO), glycerin, and propylene glycol are used as intracellular permeable cryoprotective reagents by adding them to buffers such as culture media (Patent Document 1). Of these, DMSO is the most commonly used, and has a good effect on protecting cells and organelles. However, in intracellular permeable cryopreservation solutions, the low molecular weight compounds that are cryoprotective reagents penetrate into cells, raising concerns about the effect of the cryoprotective reagents on cells (Non-Patent Document 1).

[0004] Therefore, attempts have been made to use natural cryoprotectants as cryoprotective reagents instead of chemicals. For example, it is known that disaccharides, oligosaccharides, or high molecular weight polysaccharides are added to buffer solutions such as culture media as non-permeable cryoprotective reagents.

[0005] In addition, a method of retaining a biological component in a crosslinked body that forms a hydrogel is also being considered. Patent Document 2 describes a biological component preservative made from modified hyaluronic acid, in which a side chain having a substituent that reacts with a hydroxyl group to form a crosslinked structure is introduced into raw hyaluronic acid having a weight-average molecular weight of 5,000 to 4,000,000. The modified hyaluronic acid reacts with the hydroxyl groups of a compound having multiple hydroxyl groups, such as polyvinyl alcohol, to form a crosslinked product of the modified hyaluronic acid, and the biological component is embedded in this agar-like hydrogel to be used as a preservative. It is estimated that the molecular weight of the hydrogel described in Patent Document 2 as an actual preservative is several million or more. In Patent Document 2, the biological component is preserved in a refrigerator at about 4°C for a storage period of about several days.

[0006] Patent Document 3 describes a cryopreservation composition containing a carboxylated polyamino acid in which the amino group of the polyamino acid is blocked by carboxylation (or acetylation) with a carboxylic anhydride and an organic amphoteric agent. Patent Document 4 further discloses fructan as an active ingredient of a cell preservation solution. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 63-216476 [Patent Document 2] International Publication No. 2016 / 076317 [Patent Document 3] Special Publication No. 2018-533377 [Patent Document 4] JP 2012-235728 A [Non-patent literature]

[0008] [Non-Patent Document 1] REJUVENATION RESEARCH Volume 18 Number 5,2015 Mary Ann Liebert, Inc. Summary of the Invention [Problem to be solved by the invention]

[0009] Intracellular-permeating cryoprotectants promote the dehydration of cells, thereby slowing down the rate of intracellular ice crystal formation and inhibiting ice crystal formation. DMSO in particular is easy to permeate into cells, and is therefore effective for cryopreserving cells with complex structures such as mammalian cells, but as described in the above-mentioned Non-Patent Document 1, chemicals such as DMSO are cytotoxic. It is believed that as the penetration of cryoprotectants into cells progresses and the intracellular concentration increases, the toxic effects also increase.

[0010] Furthermore, it has been reported that DMSO induces differentiation of HL-60 cells and P19CL6 cells (derived from mouse embryonal carcinoma cells) (PNAS March 27, 2001 98 (7) 3826-3831. and Biochem Biophys Res Commun. 2004 Sep 24;322(3):759-65.), and also affects differentiation of ES cells (Cryobiology. 2006 Oct;53(2):194-205.). Therefore, the use of DMSO as a cryoprotectant is not suitable for cell preservation when it is necessary to maintain the undifferentiated state and functionality of stem cells. In addition, when storing samples for a long period of time using DMSO, it is essential to store the samples in liquid nitrogen or under an atmosphere that requires careful handling, which is considered to be an issue for the dissemination of regenerative medicine and regenerative medicine research.

[0011] On the other hand, natural cryoprotectants such as sugars have affinity for cells, but their molecular size is large and they are difficult to be taken up into cells. Therefore, it is thought that adding them from outside the cells alone is not enough to suppress intracellular freezing.

[0012] As mentioned above, the tested preservative for biological components described in Patent Document 2 has a storage period of only a few days, and it is considered that a better cryopreservation technique is required to store the components for several months. In addition, in order to produce the hydrogel described in Patent Document 2, it is necessary to introduce a modification group into hyaluronic acid, and further, it is necessary to use an additive to dissolve the gel in order to recover the biological components from the hydrogel after storage. However, if such an additive is introduced into the cryopreservation method, it can be used for research and testing, but it is difficult to use it for actual medical purposes due to the risk of impurities being mixed in.

[0013] Patent Document 3 discloses a cryopreservation composition containing a carboxylated polyamino acid in which the amino group of the polyamino acid is modified with a carboxylic acid, an organic amphoteric agent, and optionally a polysaccharide; however, the survival rate of cells cryopreserved was not sufficient.

[0014] Furthermore, the fructan described in Patent Document 4 also caused cell death due to rupture or other reasons, and was not capable of adequately cryopreserving cells.

[0015] Although a method using a non-permeable cryoprotective agent is also known, such a preservation agent alone cannot provide sufficient preservation effect, although it has little effect on cells. Therefore, products that combine intracellularly permeable compounds such as DMSO, glycerin, and propylene glycol with non-permeable substances to reduce or replace the amount of compounds are commercially available. However, no cryoprotective substance that shows good cryopreservation effect and is practical, using only natural components such as biological components, has yet to be reported.

[0016] The present invention has been made in view of the above problems, and provides a solidified body in which a biological sample is preserved with a high survival rate while maintaining its properties. In particular, the solidified body contains a matrix containing water and a water-soluble polymer or a salt thereof together with the biological sample, which improves the cryopreservation effect of the biological sample, and is safe because it does not contain chemical substances such as dimethyl sulfoxide (DMSO), propylene glycol (PG), ethylene glycol (EG), serum, or serum-derived proteins. It is possible to contain proteins that are not contaminated by bacteria or viruses. In addition, the above chemical substances can be added at low concentrations that do not impair the functions of cells. Another object of the present invention is to provide a method for producing such a solidified body. [Means for solving the problem]

[0017] The present invention relates to a solidified body comprising a matrix containing an aqueous solvent and a water-soluble polymer or a salt thereof, and a biological sample, wherein the biological sample has an orthogonal projection area smaller than 1 and reduced to 1 / 3.5 or more of that in a culture solution (culture medium) before solidification, and when visible light is transmitted through the solidified body, the difference between the Munsell color system brightness of the region occupied by the biological sample and the Munsell color system brightness of the region occupied by the matrix is ​​3 or less when viewed from the light exit side, and in a differential scanning calorimeter (DSC) curve of the matrix during a temperature rise process obtained under the following measurement conditions (1) to (2) using a DSC, no endothermic peak is observed, or the temperature at which the endothermic peak is observed is greater than -1.4°C and 1.1°C or less. Note that the DSC scan is performed under the following conditions: (1) holding at 20°C for 1 minute, followed by cooling to -80°C at a cooling rate of 5°C / min, and (2) holding at -80°C for 1 minute, followed by heating to 20°C at a heating rate of 10°C / min.

[0018] In this specification, "no endothermic peak is observed" means that no endothermic peak is observed in the range of -30°C to +5°C. If water containing a water-soluble polymer shows an endothermic peak, it is generally in this range. In addition, the orthogonal projection area of ​​the biological sample and the Munsell color brightness of the region occupied by the biological sample and the matrix region are unchanged after freezing and solidifying, but if the orthogonal projection area of ​​the biological sample and the Munsell color brightness of the region occupied by the biological sample and the matrix region are temperature-dependent, the orthogonal projection area and the Munsell color brightness are measured at -80°C.

[0019] The salt of the water-soluble polymer is preferably, for example, a metal salt, a halogen salt, or a sulfate salt. The metal salt is preferably an alkali metal or an alkaline earth metal salt. The alkali metal or alkaline earth metal may be sodium, potassium, calcium, or the like. The halogen may be chlorine, bromine, or the like.

[0020] The solidified material of the present invention preferably does not contain dimethyl sulfoxide, which is an intracellularly penetrating cryoprotectant for biological samples. Also, the solidified material of the present invention preferably does not contain cryoprotectants such as ethylene glycol, which are cytotoxic to biological samples, because they are harmful to biological samples after thawing.

[0021] The solidified material of the present invention is preferably a solidified frozen material.

[0022] The solidified material preferably contains a water-soluble polymer or a salt thereof in an amount of 0.1 w / v % or more and 20 w / v % or less.

[0023] In the solidified body of the present invention, in a DSC curve during a temperature rise obtained under the above-mentioned DSC measurement conditions (1) to (2), the endothermic amount of an endothermic peak during the temperature rise is preferably 0 J / g or 65% or less of the corresponding endothermic amount of a reference solution consisting of water.

[0024] The biological sample contained in the solidified body is preferably a cell, and the cell is preferably a mammalian cell.

[0025] The biological sample contained in the solidified body is preferably a cell, and the cell is preferably a mammalian mesenchymal stem cell, a mammalian blood cell, or a mammalian endothelial cell.

[0026] The solidified body of the present invention can be preferably melted and used as a solution for administering a biological sample. The solidified body of the present invention does not contain cell-permeable and toxic compounds such as DMSO and ethylene glycol, and does not contain serum or serum-derived proteins, so that it can be used as a solution for administering a biological sample directly after melting. It is possible to add proteins that are not contaminated by bacteria or viruses. It is also possible to use a cell-permeable and toxic compound at a low concentration that does not impair the function of the cells.

[0027] It is preferable that the amount of HGF produced by the biological sample contained in a solution for administering a biological sample obtained by melting the solidified body of the present invention is suppressed compared to the amount of HGF produced by a biological sample in a solidified body containing DMSO instead of the water-soluble polymer or its salt after melting.

[0028] It is preferable that the amount of IL-10 produced by the biological sample contained in a solution for administering a biological sample obtained by melting the solidified body of the present invention is increased compared to the amount of IL-10 produced by a biological sample in a solidified body containing DMSO instead of the water-soluble polymer or its salt after melting.

[0029] The present invention also relates to a method for producing a solidified body containing a biological sample, comprising the steps of: preparing an aqueous polymer solution prepared so that, when a water-soluble polymer or a salt thereof is dissolved in an aqueous solvent and frozen at −80° C., the biological sample has an orthogonal projection area that is less than 1 and is reduced to at least 1 / 3.5 of that in a culture solution (culture medium) before solidification; and when frozen at −80° C., when visible light is transmitted through the biological sample, the difference in lightness in the Munsell color system between a region occupied by the biological sample and a region other than the region occupied by the biological sample is 3 or less, as viewed from the light exit side; and in a DSC curve during a temperature rise process obtained under the measurement conditions of the following (1) and (2) using a differential scanning calorimeter, no endothermic peak is observed, or the temperature at which an endothermic peak is observed is greater than −1.4° C. and less than 1.1° C.; incorporating the biological sample in the aqueous polymer solution; and cooling and freezing the aqueous polymer solution containing the biological sample. Here, the DSC scan was performed under the following conditions: (1) holding at 20°C for 1 minute, followed by cooling to -80°C at a rate of 5°C / min, and (2) holding at -80°C for 1 minute, followed by heating to 20°C at a rate of 10°C / min.

[0030] In this specification, "no endothermic peak is observed" means that no endothermic peak is observed in the range of -30°C to +5°C. This is because if water containing a water-soluble polymer shows an endothermic peak, it will generally be in this range.

[0031] The salt of the water-soluble polymer is preferably, for example, a metal salt, a halogen salt, or a sulfate salt. The metal salt is preferably an alkali metal or an alkaline earth metal salt. The alkali metal or alkaline earth metal may be sodium, potassium, calcium, or the like. The halogen may be chlorine, bromine, or the like.

[0032] In addition, it is preferable that the solidified body containing the biological sample of the present invention does not contain cell-permeable and cytotoxic compounds such as dimethyl sulfoxide and ethylene glycol, because these are toxic to cells after thawing. It is also preferable that serum and serum-derived proteins are not contained. However, it is possible to add proteins that are not contaminated by bacteria or viruses. It is also possible to use cell-permeable and toxic compounds at low concentrations that do not impair the functions of cells.

[0033] A preferred method for producing a solidified body is one in which the step of cooling and freezing the aqueous polymer solution containing the biological sample is carried out by cooling and freezing the aqueous polymer solution to a temperature of -27°C or lower using a slow freezing method at a cooling rate of 10°C / min or less.

[0034] In the method of the present invention for producing a solidified body containing a biological sample, the temperature range for cooling and freezing the aqueous polymer solution containing the biological sample is not limited as long as it is -27°C or lower, but the upper limit is desirably -70°C or lower, preferably -80°C or lower, and the lower limit is desirably -196°C or higher, preferably -150°C or higher.

[0035] In the method of the present invention for producing a solidified body containing a biological sample, the cooling rate for cooling and freezing the aqueous polymer solution containing the biological sample is preferably 10°C / min or less, and more preferably 1°C / min or less, and the cooling and freezing process is preferably carried out by a slow freezing method.

[0036] In the method of the present invention for producing a solidified body containing a biological sample, the solidified body preferably contains a water-soluble polymer or a salt thereof in an amount of 0.1 w / v % or more and 20 w / v % or less.

[0037] In the method of the present invention for producing a solidified body containing a biological sample, it is preferable that the endothermic amount of an endothermic peak in the temperature rise process of a DSC curve obtained under the above-mentioned DSC measurement conditions (1) to (2) for an aqueous solution of a water-soluble polymer or its salt is 0 J / g or 65% or less of the corresponding endothermic amount of a reference solution consisting of water.

[0038] According to the present invention, it is possible to provide a solidified body containing a biological sample such as a cell whose properties are appropriately maintained without using a cell-permeable and toxic compound such as DMSO or ethylene glycol, which is an intracellular-permeable cryoprotectant. The water-soluble polymer or its salt used in the present invention is an intracellular non-permeable type, and therefore exhibits a high cryoprotective effect on the biological sample despite its low toxicity to the biological sample, and therefore the biological sample in the solidified body is preserved with a high survival rate.

[0039] In addition, the solidified body of the present invention does not contain serum or serum-derived proteins to prevent damage to the biological sample in the solidified body, and therefore is not contaminated by bacteria or viruses. Since there is no risk of containing unknown components or infectious substances derived from living organisms, the solidified body of the present invention can be used as it is as a solution for administering biological samples after melting. Therefore, it is considered to be suitable for storing biological samples for regenerative medicine, for example. It is possible to use proteins that are not contaminated by bacteria or viruses. It is also possible to use compounds that are cell-permeable and toxic at low concentrations that do not impair cell functions.

[0040] The water-soluble polymer or its salt forming the matrix of the solidified body of the present invention is dissolved in an aqueous solvent. Therefore, the matrix of the solidified body of the present invention may contain components derived from the aqueous solvent in addition to water and the water-soluble polymer or its salt. Preferred aqueous solvents that can be used in the present invention include water, physiological solutions, and isotonic aqueous solutions in which the salt concentration, sugar concentration, etc. are adjusted with sodium ions, potassium ions, calcium ions, etc. so that the osmotic pressure is approximately the same as that of body fluids or cell fluids. Specifically, the aqueous solvent may be, for example, water, physiological saline, physiological saline having a buffering effect such as phosphate buffered saline (PBS), Dulbecco's phosphate buffered saline, Tris buffered saline (TBS), HEPES buffered saline, balanced salt solutions such as Hank's balanced salt solution, Ringer's solution, lactate Ringer's solution, acetate Ringer's solution, bicarbonate Ringer's solution, or basal culture media for animal cell culture such as D-MEM, E-MEM, αMEM, RPMI-1640 medium, Ham's F-12, Ham's F-10, M-199, general culture media for various cells or tissues, commercially available culture media, etc. However, it is preferable that the aqueous solvent of the present invention does not contain DMSO, ethylene glycol, serum, or serum-derived proteins. It is possible to add proteins that are not contaminated by bacteria or viruses. It is also possible to use compounds that are cell-permeable and toxic at low concentrations that do not impair the function of cells. Effect of the Invention

[0041] According to the solidified body of the present invention, a biological sample such as a cell can be cryopreserved in a matrix containing water and a water-soluble polymer or its salt while maintaining the viability and properties of the biological sample without using a cryoprotectant such as highly toxic DMSO or ethylene glycol. The water-soluble polymer or its salt used in the present invention, which can function as a cryoprotectant in the solidified body of the present invention, can promote dehydration from the biological sample during freezing, thereby realizing a good vitrification state inside and outside the biological sample. The water-soluble polymer or its salt in the present invention is not cell membrane permeable. Therefore, during vitrification of a biological sample such as a cell, it does not penetrate into the biological sample and cause the biological tissue to swell, and as a result, the biological sample contained in the solidified body of the present invention has a reduced orthogonal projection area compared to that in the culture solution (culture medium) before solidification. In the water-soluble polymer of the present invention, by adjusting the molecular species and polymerization degree (molecular weight) of the water-soluble polymer and / or by adding a low molecular weight or monomolecular compound to the aqueous solution of the water-soluble polymer, the temperature and heat of the endothermic peak of melting during the heating process, and the difference in visible light transmittance between the solvent partial region of the solidified body and the region inside the biological sample can be adjusted. In the present invention, the cryopreservation effect of biological tissues such as cells can be improved by adjusting the DSC of the aqueous polymer solution so that no endothermic peak is observed or the endothermic peak appears near the endothermic peak of standard water (ultrapure water), and by adjusting the difference in brightness when visible light is irradiated between the solvent region of the solidified body and the region within the biological sample.

[0042] The solidified body of the present invention does not contain intracellular penetrating chemicals such as DMSO and ethylene glycol. Therefore, damage to biological samples, cytotoxicity, and effects on cell properties as reported for DMSO can be suppressed to a low level. Even after the solidified body is melted, the properties of the biological sample can be appropriately maintained.

[0043] Furthermore, the solidified body of the present invention makes it possible to maintain the viability and properties of the biological sample without containing serum and / or serum-derived proteins, and therefore the biological sample will not be contaminated with bacteria or viruses.

[0044] The solidified material of the present invention can be easily produced by slowly freezing an aqueous polymer solution containing a biological sample. The solidified material obtained can be stably stored for a long period of time at a temperature of -27°C or lower, i.e., in a deep freezer, even though no cytotoxic chemicals such as DMSO or ethylene glycol or proteins such as serum are used. It is possible to add proteins that are not contaminated by bacteria or viruses. It is also possible to use compounds that are cell-permeable and toxic at low concentrations that do not impair cell functions.

[0045] The range of the cryopreservation temperature is not limited as long as it is −27° C. or lower, but the upper limit is desirably −70° C. or lower, preferably −80° C. or lower. The lower limit is desirably −196° C. or higher, preferably −150° C. or higher. [Brief description of the drawings]

[0046] [Figure 1] FIG. 1 is a graph showing the cell viability of primary human mesenchymal stem cells cryopreserved using the test sample solution of the present invention. [Figure 2A] FIG. 1 is a diagram showing the analysis results of a test sample solution by differential scanning calorimetry. [Figure 2B] FIG. 2 is an enlarged view showing the analysis results of a test sample solution by differential scanning calorimetry. [Figure 3A] FIG. 1 is a diagram showing the analysis results of a test sample solution containing ultrapure water by differential scanning calorimetry. [Figure 3B] FIG. 1 shows the analysis results of a test sample solution containing DMSO as a cryoprotectant by differential scanning calorimetry. [Figure 3C] FIG. 2 is a diagram showing the analysis results of a test sample solution containing the test sample of Example 1 by differential scanning calorimetry. [Figure 4A] FIG. 1 is a graph showing the long-term preservation effect of primary human mesenchymal stem cells cryopreserved using the test sample solution of the present invention. [Figure 4B]FIG. 1 is a graph showing the long-term preservation effect of primary human mesenchymal stem cells during refrigerated storage using the test sample solution of the present invention. [Figure 5A] FIG. 1 shows the amount of HGF produced in primary human mesenchymal stem cells after cryopreservation using the test sample solution of the present invention. [Figure 5B] FIG. 1 is a graph showing the amount of IL-10 produced in primary human mesenchymal stem cells after cryopreservation using the test sample solution of the present invention. [Figure 6] FIG. 1 shows the expression levels of undifferentiation biomarkers in primary human mesenchymal stem cells after cryopreservation using the test sample solution of the present invention. [Figure 7A] FIG. 1 shows the intracellular vitrification state after freezing in a control test (Comparative Example 2). [Figure 7B] FIG. 1 shows the intracellular vitrification state after freezing using the test sample solution of Comparative Example 1. [Figure 7C] FIG. 2 shows the state of intracellular vitrification using the test sample solution of Example 1. [Figure 8A] FIG. 13 is a diagram showing the brightness difference in the intracellular vitrification state. [Figure 8B] The brightness difference within the cell in the vitrified state was converted into a numerical value according to the Munsell scale (0 to 10), and this is a graph showing the brightness difference between the solvent and the inside of the cell. [Figure 9] FIG. 1 is a graph showing the cryoprotective effect on various cells during cryopreservation using the test sample solution of the present invention. [Figure 10] FIG. 1 shows the cell viability of primary canine mesenchymal stem cells cryopreserved using low molecular weight saccharides. [Figure 11A] FIG. 1 shows the results of HPLC analysis of test samples from various production examples. [Figure 11B] FIG. 1 shows the results of HPLC analysis of test samples from various production examples. [Figure 11C] FIG. 1 shows the results of HPLC analysis of test samples from various production examples. [Figure 11D] FIG. 1 shows HPLC analysis results for a calibration curve of saccharides having a given number of sugars. [Figure 12]FIG. 2 shows the results of HPLC analysis of a test sample having a polymer chain of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0047] The solidified body of the present invention is a solidified body comprising a matrix containing water and a water-soluble polymer or a salt thereof, and a biological sample. In the solidified body of the present invention, the biological sample has an orthogonal projection area smaller than 1 and reduced to 1 / 3.5 or more compared to that before solidification.

[0048] In the present invention, the "orthogonal projection area" of a biological sample refers to the area calculated by taking an image of the biological sample from above in the normal direction of the cooling stage when the biological sample is observed on a cooling stage for a microscope, and calculating the area of ​​the biological sample in the image using the image analysis software ImageJ (https: / / imagej.nih.gov / ij / ).

[0049] In the solidified body of the present invention, the volume of the biological sample in the solidified body is reduced compared to the biological sample before freezing, as a result of the promotion of the discharge of water from the biological sample during freezing and solidification. By effectively dehydrating the inside of the cells in this way, damage to the cells during freezing is significantly reduced, the cells are protected, and when the solidified body is thawed, the biological sample, such as the cells, contained in the solidified body shows a high survival rate.

[0050] In the solidified body of the present invention, the inside of the biological sample is dehydrated, so that the formation of ice crystals in the biological sample is suppressed or prevented, and the matrix portion containing water and a water-soluble polymer or its salt and the inside of the biological sample are in a good vitrified state. Therefore, ice crystals are not formed in the matrix portion or in the biological sample. When ice crystals with large crystal grains are formed, when visible light is transmitted through the solidified body, the visible light is blocked, and the brightness of the ice crystal portion decreases. In the solidified body of the present invention, the matrix portion of the solidified body and the inside of the biological sample are formed in a similar frozen state, that is, are vitrified in the same manner, so that when visible light is transmitted through the solidified body in the frozen state of the present invention, the brightness of the inside of the biological sample in the solidified body and the brightness of the matrix portion in the solidified body, i.e., the brightness of the area other than the inside of the biological sample, are close when viewed from the light exit side. Preferably, the difference in brightness in the Munsell color system between the area occupied by the biological sample and the area occupied by the matrix is ​​3 or less. It is also preferable that the frozen and solidified matrix portion and the inside of the biological sample are not darkened due to ice crystal formation.

[0051] Usually, the freezing method called vitrification is a method in which solutes (cryoprotectants to prevent freezing damage) are eliminated from the crystals when the solution freezes, increasing the salt concentration in the remaining solution, and an osmotic pressure difference occurs between the inside and outside of the cell, dehydrating the inside of the cell and vitrifying the inside of the cell. This method is applied to cells with particularly low survival rates after thawing. In this method, the concentration of solutes (cryoprotectants) is increased and the cooling rate is increased to make it easier to vitrify water. However, it has been known that increasing the osmotic pressure difference can cause greater damage to cells, and that recrystallization can occur during thawing, damaging the cells. In addition, the method is technically difficult.

[0052] In the present invention, dehydration from a biological sample and its promotion are achieved by a matrix containing a water-soluble polymer or its salt and water. The matrix of the present invention can effectively trap aqueous solvent molecules within the matrix formed by the polymer chains during the cooling process. This restricts the molecular motion of water in the aqueous solvent during cooling, allowing the water to be solidified and / or frozen in a vitrified state without crystallizing, i.e., without forming ice crystals.

[0053] During solidification and freezing, the water-soluble polymer used in the present invention forms an amorphous glassy matrix due to the action of its polymer chains. In the solidified body of the present invention, the water molecules of the solvent are thought to exist in the network matrix of the polymer and to exist in the state of free water or bound water (water molecules are entangled and captured by the polymer). In addition, water molecules that have been expelled from inside cells, etc. due to the osmotic pressure difference during solidification and freezing are thought to be replaced with the polymer surrounding the biological sample, such as cells. This replacement can further promote the movement of water molecules from inside the biological sample to the outside. As a result, the formation of ice crystals in the biological sample is suppressed and prevented, and the inside of the biological sample is in a vitrified state.

[0054] That is, in the solidified body of the present invention, both the inside and outside of the biological sample are vitrified by the action of the polymer chains of the water-soluble polymer, so that it is possible to weaken the osmotic shock in the biological sample during freezing, which is a problem in conventional vitrification methods. Therefore, it is not necessary to contain chemical substances such as dimethyl sulfoxide (DMSO) or ethylene glycol, which have cytotoxicity, and the solidified body of the present invention does not contain DMSO and / or ethylene glycol.

[0055] The solidified body of the present invention contains a matrix having such excellent vitrification ability. In such a matrix of the present invention, in a DSC curve during a temperature rise obtained using a differential scanning calorimeter (DSC) under the following measurement conditions (1) and (2), no endothermic peak is observed as measured by DSC, or the temperature at which the endothermic peak is observed is higher than -1.4°C and equal to or lower than 1.1°C. DSC conditions: (1) Hold at 20°C for 1 minute, then cool to -80°C at a rate of 5°C / min, and (2) After holding at -80°C for 1 minute, increase the temperature to 20°C at a rate of 10°C / min.

[0056] That is, in the matrix of the present invention, the endothermic peak presumed to be due to the melting of water is not observed during the temperature rise process of the matrix, or if observed, it is in the range of more than -1.4°C and less than 1.1°C, that is, near the temperature (0.7°C) at which an endothermic peak is observed in ultrapure water in DSC measurement under the same conditions. For vitrification in a biological sample such as a solvent or a cell, it generally seems desirable to use a solution having a lower melting point (freezing point). However, the present inventors have found that for good vitrification of a biological sample during freezing, it is desirable for the matrix to have the opposite characteristic to this technical common sense. Usually, the phenomenon that the melting point (freezing point) is lower than that of water occurs when a solute is dispersed in a matrix of water, but in the matrix containing a water-soluble polymer of the present invention, conversely, water molecules are present in the polymer network matrix in the aqueous solvent formed by the water-soluble polymer, and water does not freeze in the polymer matrix, but exists as free water, or even if water freezes, it freezes in a state where it is entangled in the polymer (bound water). For this reason, in the aqueous polymer solution of the present invention, it is presumed that no endothermic peak due to the melting of water is observed during the temperature increase process, or that the endothermic peak is observed at a temperature close to that at which the endothermic peak of pure water is observed.

[0057] As the water-soluble polymer capable of forming such a matrix of the present invention, for example, a polymer containing a monomer having a hydrophilic group as a repeating unit can be used. Here, the hydrophilic group is, for example, a hydroxyl group and a carboxylic acid group and a salt thereof. The water-soluble polymer may also contain a nitrogen-containing monomer having an amino group which may be substituted or an amide group which may be substituted as a repeating unit. In particular, it may be preferable that the water-soluble polymer structure has a hydroxyl group at an equatorial position. This is because it is believed that the water of the solvent can be more effectively trapped in the matrix formed by the polymer chain during freezing.

[0058] The monomer having a hydrophilic group is, for example, a sugar residue. In this case, the polymer used in the present invention may be a water-soluble polymer including a polymer in which sugar residues are bonded as repeating units through glycosidic bonds and derivatives thereof. Examples of sugar residues include, but are not limited to, monosaccharides, or monosaccharides in which the hydroxyl and / or hydroxymethyl groups of the monosaccharides are substituted, for example, monosaccharides in which the hydroxyl and / or hydroxymethyl groups are substituted with at least one substituent selected from the group consisting of a carboxyl group, an amino group, an N-acetylamino group, a sulfoxy group, a methoxycarbonyl group, and a carboxymethyl group.

[0059] Examples of monosaccharides include triose, tetrose, pentose, hexose, and heptose. For example, examples of pentoses include ribose, arabinose, xylose, lyxose, xylulose, ribulose, and deoxyribose. Examples of hexoses include glucose, mannose, galactose, fructose, sorbose, tagatose, fucose, fuculose, and rhamnose.

[0060] For example, the monosaccharide substituted with a carboxyl group includes uronic acid. Examples of the uronic acid include glucuronic acid, iduronic acid, mannuronic acid, and galacturonic acid. Examples of the monosaccharide substituted with an amino group include amino sugars. Examples of the amino sugar include glucosamine, galactosamine, mannosamine, and muramic acid. Examples of the monosaccharide substituted with an N-acetylamino group include N-acetylglucosamine, N-acetylmannosamine, N-acetylgalactosamine, and N-acetylmuramic acid. Examples of the monosaccharide substituted with a sulfooxy group include galactose-3-sulfate. Examples of the monosaccharide having multiple substituents include N-acetylglucosamine-4-sulfate, iduronic acid-2-sulfate, glucuronic acid-2-sulfate, N-acetylgalactosamine-4-sulfate, neuraminic acid, and N-acetylneuraminic acid.

[0061] For example, the water-soluble polymer used in the present invention is a polymer containing the above-mentioned monosaccharides as repeating units. For example, the water-soluble polymer in the present invention may be a polymer containing pentose, hexose, or uronic acid, or a combination thereof, which may be substituted, as a repeating unit. For example, the water-soluble polymer in the present invention may contain a six-membered ring structure in its main chain. This is because polysaccharides having a six-membered ring structure in their main chain may easily form a polymer network structure around cells through hydrogen bonds. In addition, the water-soluble polymer in the present invention may be an alternating copolymer of a monomer having a hydrophilic group and a nitrogen-containing monomer. The nitrogen-containing monomer may be, for example, an amino sugar. In this case, for example, the water-soluble polymer in the present invention may be a glycosaminoglycan. It may also be a sulfated polysaccharide in which one or more hydroxyl groups are substituted with sulfooxy groups. Although not limited thereto, examples of the polymer in the present invention include hyaluronic acid, dextran, pullulan, and chondroitin sulfate.

[0062] The water-soluble polymer or its salt in the present invention may be naturally derived or may be chemically synthesized. A commercially available water-soluble polymer or its salt may be used as it is. A naturally derived polymer compound or a commercially available polymer compound having a larger molecular weight may be used, and the cleavage product may be obtained by subjecting it to hydrolysis, enzyme treatment, subcritical treatment, or the like, and the molecular weight may be adjusted to form the water-soluble polymer in the present invention. In addition, each monomer may be naturally derived, may be modified or substituted, or may be chemically synthesized. For example, preferably, the monomer contained in the water-soluble polymer in the present invention is a biological component. It is considered that the cytotoxicity is low when a biological sample is mixed or stored in a matrix containing the water-soluble polymer. In addition, the process required for conventional cryopreservation solutions, such as washing and removing cell protective components from a biological sample after thawing and / or melting the solidified body, may be unnecessary or simplified.

[0063] In the cooling process, water molecules are efficiently trapped in the matrix formed by the polymer chains of the water-soluble polymer of the present invention, so that in the present invention, for example, the intrinsic viscosity of the polymer aqueous solution in which the water-soluble polymer or its salt is dissolved in an aqueous solvent can be adjusted to about 0.20 to 0.95 dL / g. If the intrinsic viscosity of the polymer aqueous solution is too small, the polymer will diffuse, and water molecules cannot be entangled and captured in the network of the water-soluble polymer. On the other hand, if the intrinsic viscosity of the polymer aqueous solution is too high, replacement with water molecules near the biological sample will not proceed. In addition, a problem may occur in that the handling properties deteriorate when the biological sample is contained in the polymer solution for cryopreservation of the biological sample. By setting the intrinsic viscosity of the polymer aqueous solution to a range of about 0.20 dL / g or more and 0.95 dL / g or less, when the polymer aqueous solution is cooled, the amorphous glass state in the frozen state can be stabilized. For this reason, it is considered that the biological sample is less likely to be damaged by cooling and freezing, and the biological sample is efficiently preserved in the solidified body while maintaining a stable and high viability. The destruction of cells in the biological sample due to the formation of ice crystals is also unlikely to occur, and therefore the survival rate of cells in the biological sample in solution after melting the solidified body of the present invention is high.

[0064] The "intrinsic viscosity (η)" of the aqueous solution of the water-soluble polymer or its salt used in the present invention means a value calculated by the following method and formula.

[0065] Intrinsic viscosity measurement: (1) Dissolve a specified amount of NaCl in ion-exchanged water at 30°C to prepare a 0.2 M NaCl solution (standard solution). (2) A sample of the water-soluble polymer or its salt is dissolved in a standard solution at 30°C to prepare a stock solution. When a sample of the water-soluble polymer or its salt is obtained in the form of a solution, the solid portion obtained by removing the solvent from the solution is used as the sample of the water-soluble polymer or its salt. In the case of a mixed sample containing multiple water-soluble polymers, the mixture is used as a sample as is. Even if the water-soluble polymer contains impurities, the mixture is used as a sample as is. However, this does not apply when measuring the viscosity average molecular weight described below. In the case of a mixed sample containing multiple water-soluble polymers, each water-soluble polymer is separated and fractionated, and the solvent is removed from each solution to use as a sample of each water-soluble polymer. In addition, if the water-soluble polymer is unknown, the substance is identified by HPLC, LC-MS, LC-IR, etc., and the viscosity average molecular weight is calculated as described below. In addition, if the water-soluble polymer contains multiple unknown water-soluble polymers, each component is separated and fractionated, and the substance is identified by HPLC, LC-MS, LC-IR, etc., and the viscosity average molecular weight is calculated as described below. In addition, even if the water-soluble polymer contains impurities, if the mixture does not affect the viscosity (for example, impurities such as metal salts), the mixture is used as the sample of the water-soluble polymer. If impurities that affect the calculation of the viscosity average molecular weight are contained, remove the impurities or fractionate the water-soluble polymer before measurement. At this time, measure the viscosity of each of the standard solution and the stock solution, and adjust the relative viscosity of the stock solution to the standard solution to be 2.0 to 2.4. (3) Dilute the 30°C stock solution 5 / 4, 5 / 3, and 5 / 2 times with the 30°C standard solution. (4) Measure the viscosity of the standard solution, undiluted solution, and diluted solution at 30°C. Use an E-type viscometer to measure the viscosity. (5) The viscosity of the original solution and the diluted solution divided by the viscosity of the standard solution is the relative viscosity (η r ) and derive the reduced viscosity based on the following formula: TIFF2025061934000001.tif2146Here, η sp : Reduced viscosity of water soluble or its salt [mL / g], η r : relative viscosity of the water-soluble polymer or its salt [-], C: concentration of the water-soluble polymer or its salt [g / mL]. (6) Plot the relationship between the concentration of the water-soluble polymer or its salt and the reduced viscosity of the water-soluble polymer or its salt, and draw an approximate line. The intercept of the approximate line (where the polymer or sugar concentration is 0) is taken as the limiting viscosity of the aqueous solution of the water-soluble polymer or its salt.

[0066] The intrinsic viscosity of a polymer aqueous solution can be adjusted by selecting the molecular species and degree of polymerization (viscosity average molecular weight) of the water-soluble polymer.

[0067] For example, the water-soluble polymer or its salt used in the present invention is, for example, a water-soluble polymer or its salt having a viscosity-average molecular weight of more than 3000 and not more than 500000. By using a water-soluble polymer or its salt having such a viscosity-average molecular weight, when a matrix containing the water-soluble polymer is cooled, the amorphous glassy state in the frozen state is stabilized. Therefore, the cells are protected by the matrix during cooling and freezing, and as a result, the cells are less likely to be damaged, and the cells can be stably and efficiently cryopreserved in the solidified body. Therefore, the survival rate of cells in the biological sample after thawing the solidified body after cryopreservation is high. If the viscosity-average molecular weight of the water-soluble polymer is 3000 or less, vitrification may not occur well. In addition, if the viscosity-average molecular weight of the water-soluble polymer is more than 500000, the viscosity increases significantly, and the solubility decreases, or the prepared solution foams, which may cause problems such as poor handling. The viscosity-average molecular weight is preferably, for example, 10000 or more. Further, polymers having a viscosity average molecular weight of 400,000 or less, more preferably 200,000 or less, and particularly preferably 150,000 or less, are preferred, because the viscosity of the aqueous solution can be adjusted to a low level and the solution is easy to handle.

[0068] The "viscosity average molecular weight" of the water-soluble polymer or salt used in the present invention is calculated by the following method and formula using the intrinsic viscosity (η) calculated by the above method and formula.

[0069] Viscosity average molecular weight: The viscosity average molecular weight is calculated from the intrinsic viscosity. TIFF2025061934000002.tif3559The viscosity average molecular weight M is calculated from the intrinsic viscosity obtained by measurement and the values ​​of K and α published in the literature, etc., in the Mark Hoying-Sakurada formula above. For example, if the water-soluble polymer is hyaluronic acid, K = 3.6 × 10 -4 and α = 0.78. In the case of pullulan and gelatin, K = 9 × 10 -4 , α=0.5, and for dextran, K=6.3×10 -8 , α = 1.4, and for chondroitin sulfate, K = 5.8 × 10 -4 , α = 0.74, for fructan, K = 1.6 × 10 -3 , α = 0.45, and carboxylated polylysine has a K = 2.78 × 10 -5 , α=0.87.

[0070] K and α are values ​​that vary depending on the type of polymer. For example, the values ​​of K and α are disclosed in many published documents, such as the "Polymer Materials Handbook" (edited by the Society of Polymer Science). Using these published values, the viscosity average molecular weight can be calculated from the intrinsic viscosity (η).

[0071] In the present invention, the molecular weight calculated by this method is regarded as the viscosity average molecular weight. In the case of monosaccharides and disaccharides such as sucrose and glucuronic acid, and compounds considered to be monomolecular, the molecular weight is clearly specified from the structural formula, so the molecular weight specified from the structural formula is treated as the viscosity average molecular weight.

[0072] The hydrophilic groups of the water-soluble polymer or its salt used in the present invention are preferably unmodified or, even if modified, are less than 50% of the total number of hydrophilic groups, i.e., no substituents are introduced into the polymer chain or, even if they are introduced, are less than 50% of the total number of hydrophilic groups. It is presumed that the hydrophilic groups of the water-soluble polymer, especially the OH group, NH2 group, and COOH group, contribute to the protection of the biological sample, the vitrification of the matrix, and the replacement with water molecules around the biological sample, so that it is advantageous to improve the survival rate of the biological sample if these functional groups are not modified. Furthermore, when a functional group is introduced into the water-soluble polymer, the reagent used to modify the hydrophilic group of the polymer may adversely affect the cryoprotective effect of the polymer or may make it impossible to use it as a cryopreservation solution for cryopreservation of biological samples for regenerative medicine purposes.

[0073] Furthermore, the present inventors have found that in the present invention, the endothermic peak of a matrix containing water and a water-soluble polymer or a salt thereof can be adjusted by adding a saccharide or a salt thereof having a lower molecular weight than the water-soluble polymer to an aqueous polymer solution containing the water-soluble polymer or a salt thereof. Thus, the matrix of the present invention may further contain a low molecular weight saccharide or a salt thereof in addition to the water-soluble polymer.

[0074] The low molecular weight sugars or their salts are held in the polymer matrix by hydrogen bonds due to the hydrophilic groups in the water-soluble polymer. As a result, it is believed that the amount and balance of water present as free water and bound water trapped in the polymer matrix is ​​changed. Furthermore, it is believed that the low molecular weight sugars or their salts also have the effect of further promoting dehydration in the biological sample during the freezing process. That is, it is presumed that the presence of a polymer holding low molecular weight sugars or their salts around a biological sample such as a cell causes the water molecules near the cell membrane to be replaced with low molecular weight sugars. Therefore, it is believed that the water discharged from the biological sample such as a cell due to the osmotic pressure difference during freezing is replaced not only by the polymers around the biological sample such as the cell, but also by low molecular weight sugars. Therefore, it is believed that the addition of low molecular weight sugars or their salts helps to discharge water from within the biological sample, and by replacing it with water molecules, the formation and growth of ice crystals near the cell membrane is suppressed or prevented. For example, by setting the limiting viscosity of the aqueous polymer solution to a range of 0.20 dL / g or more and 0.95 dL / g or less, the replacement of water molecules with low molecular weight sugars can be promoted. As a result, cell membrane damage during freezing can be significantly suppressed. In other words, the low molecular weight saccharide or its salt can function as a component for cell protection in the aqueous polymer solution. If the intrinsic viscosity of the aqueous polymer solution is too small, the low molecular weight saccharide will diffuse in the polymer solution, and water molecules may not be efficiently entangled and captured in the water-soluble polymer network. On the other hand, if the intrinsic viscosity of the aqueous polymer solution is too high, it is believed that the exchange of low molecular weight saccharide with water molecules does not proceed efficiently.

[0075] In order to retain low molecular weight saccharides or their salts in the matrix, it is desirable that the hydrophilic groups of the water-soluble polymer or its salt used in the present invention are not modified, or even if modified, the total number of hydrophilic groups is 50% or less, that is, no substituent is introduced into the polymer chain, or even if it is introduced, the total number of hydrophilic groups is 50% or less. If the hydrophilic group of the water-soluble polymer is modified, the retention effect of the low molecular weight saccharides or their salts by the hydrophilic group is reduced, and even if low molecular weight saccharides coexist, it may not be possible to fully contribute to improving the survival rate of the biological sample. Therefore, for example, it may not be preferable to modify the OH group or NH2 group of the water-soluble polymer with a carboxylic acid or the like.

[0076] The low molecular weight saccharide or its salt used in the present invention is, for example, a saccharide or its salt having a viscosity average molecular weight of 3000 or less. Preferably, it may be a monosaccharide, disaccharide, oligosaccharide, or the like having a viscosity average molecular weight of 1000 or less.

[0077] The low molecular weight saccharide in the present invention may be, for example, the monosaccharide described above as a monomer constituting a water-soluble polymer. For example, the low molecular weight saccharide is glucose, fructose, galactose, or uronic acid in which the alcohol group of these is oxidized, or an amino sugar in which the alcohol group is substituted with an amino group, sucrose, trehalose, or a polymer or combination thereof. In addition, the low molecular weight saccharide may be, for example, a fragment of a polymer, such as hyaluronic acid, dextran, pullulan, or chondroitin sulfate. Although not particularly limited as long as it does not impair the effect of the present invention, the low molecular weight saccharide may be, for example, a cleavage product (fragment) of glycosaminoglycan, that is, a monosaccharide constituting glycosaminoglycan, a disaccharide thereof, or an oligosaccharide thereof. In the case of hyaluronic acid, it is preferable to use one having a viscosity average molecular weight of 1000 or less.

[0078] Preferably, low molecular weight saccharide is the cleavage product of hyaluronic acid.Therefore, preferably, low molecular weight saccharide or its salt used in the present invention is glucuronic acid or N-acetylglucosamine, or the disaccharide or oligosaccharide thereof, or its salt.Preferably, saccharide can be glucuronic acid or its modified compound, or its disaccharide or oligosaccharide, or its salt.

[0079] The term "cleavage product" as used herein means a compound having a smaller molecular weight than the original polymer, which is considered to be obtained when a polymer is subjected to hydrolysis, enzyme treatment, subcritical treatment, or the like. For example, the polymer in the present invention may be a water-soluble polymer obtained by treating a larger polymer compound as described above, and the low molecular weight saccharide in the present invention may be a low molecular weight saccharide obtained by treating the water-soluble polymer in the present invention. In the present invention, the cleavage product may be a monomer that is a component of the original polymer and / or a polymer of the monomer having various degrees of polymerization and / or a mixture thereof.

[0080] "Subcritical processing" means contacting the raw material to be extracted with a subcritical fluid as an extracting solvent that has been brought into a subcritical state under conditions of a predetermined temperature and a predetermined pressure. For example, when water is raised to a pressure of 22.12 MPa or more and a temperature of 374.15°C or more, it is in a state that is neither liquid nor gas. This point is called the critical point of water, and hot water with a temperature and pressure close to the critical point is called subcritical water. Using the hydrolysis action of this subcritical water, the desired components can be obtained from the raw material to be extracted. In the present invention, the conditions for subcritical processing are, for example, a temperature of 150°C or more and 350°C or less, and the subcritical processing pressure can be equal to or higher than the saturated vapor pressure at each temperature, but can be, for example, 0.5 MPa or more and 25 MPa or less. After the subcritical processing, components with a molecular weight of less than a predetermined value are separated and collected, and can be used as the cleavage product of the present invention. In addition, there are no particular limitations on the hydrolysis or enzyme processing, and reagents and processing methods that are commonly used can be used without problems.

[0081] The water-soluble polymer and low molecular weight saccharides used in the present invention may be obtained simultaneously by a single subcritical treatment. That is, the water-soluble polymer and low molecular weight saccharides in the present invention may be a subcritical treatment product of a polymer compound having a first molecular weight distribution in a molecular weight range of more than 3000 and not more than 500000 as a viscosity average molecular weight, and a second molecular weight distribution in a molecular weight range of not more than 3000 as a viscosity average molecular weight. Therefore, for example, a method for producing an aqueous polymer solution may include a step of obtaining the water-soluble polymer and low molecular weight saccharides used in the present invention by dissolving a polymer, which is a polysaccharide having a molecular weight of more than 500000 as a viscosity average molecular weight, in water and then performing an extraction treatment under subcritical conditions of water. However, the water-soluble polymer and low molecular weight saccharides used in the present invention may be used in combination with those treated and / or separated based on molecular weight in separate treatment steps.

[0082] The aqueous solution of low molecular weight saccharide or its salt in the present invention shows its endothermic peak at a temperature lower than the temperature (0.7℃) at which the endothermic peak is observed in pure water by DSC measurement.For example, the hyaluronic acid with viscosity average molecular weight of 1000 or less shows its endothermic peak at -8.1℃, which is lower than the endothermic peak temperature of pure water, 0.7℃.

[0083] On the other hand, the water-soluble polymer or its salt used in the present invention, for example, has an endothermic peak temperature of -1.4°C for hyaluronic acid with a viscosity average molecular weight of 15000, and 1.49°C for pullulan with a viscosity average molecular weight of 373000. According to the present invention, when such a water-soluble polymer or its salt is combined with a low molecular weight saccharide or its salt, the endothermic peak temperature of the polymer aqueous solution approaches the endothermic peak temperature of pure water, or the endothermic peak itself is not observed in the measurement by DSC. For example, when hyaluronic acid with a viscosity average molecular weight of 1000 or less is added to hyaluronic acid with a viscosity average molecular weight of 15000, the endothermic peak temperature does not decrease, but increases to -0.4°C. On the other hand, when hyaluronic acid with a viscosity average molecular weight of 1000 or less is added to pullulan with a viscosity average molecular weight of 373000, the endothermic peak temperature decreases to 0.83°C.

[0084] That is, when the hyaluronic acid with viscosity average molecular weight of 1000 or less is mixed with the water-soluble polymer whose endothermic peak temperature is lower than that of pure water, the endothermic peak temperature rises and approaches the endothermic peak temperature of pure water, or the endothermic peak itself does not appear in DSC.In addition, when the hyaluronic acid with viscosity average molecular weight of 1000 or less is mixed with the water-soluble polymer whose endothermic peak temperature is higher than that of pure water, the endothermic peak temperature drops and approaches the endothermic peak temperature of pure water, or the endothermic peak itself does not appear in DSC.In this way, for example, by using the hyaluronic acid with viscosity average molecular weight of 1000 or less, the endothermic peak temperature of water-soluble polymer can be adjusted to be around the endothermic peak temperature of pure water, which is 0.7℃.

[0085] The low molecular weight saccharide or its salt that has such an effect is not limited to the above-mentioned hyaluronic acid with a viscosity average molecular weight of 1000 or less. As long as the viscosity average molecular weight is 1000 or less, other saccharides such as sucrose, trihalose, etc., other than hyaluronic acid, can have the same effect. In the freezing and solidifying process of the matrix of the present invention, it is speculated that the low molecular weight saccharide exists between water molecules to inhibit the ice crystallization of water, or cooperates with the water-soluble polymer network to trap water in the network (either bound water or free water), thereby inhibiting the ice crystallization of water in the first place, so that the polymer aqueous solution of the present invention can realize the behavior close to that of pure water.

[0086] Therefore, in the solidified body of the present invention, the appearance temperature of the endothermic peak can be adjusted by adding a compound such as a low molecular weight saccharide to the water-soluble polymer, which indicates that the state of trapping water molecules in the polymer network can be adjusted by bringing the appearance temperature of the endothermic peak closer to that of pure water, or by preventing the appearance of an endothermic peak. Therefore, in the solidified body of the present invention, the protective effect on the biological sample contained in the solidified body is adjusted to be appropriate.

[0087] Furthermore, in the solidified body of the present invention, by adding a compound such as a low molecular weight saccharide to the water-soluble polymer, the difference in brightness in the Munsell color system between the region occupied by the biological sample in the solidified body and the region occupied by the matrix in the solidified body can be adjusted to 3 or less. This shows that the degree of ice crystal formation in the biological sample, i.e., the degree of vitrification, can be adjusted by adding a compound such as a low molecular weight saccharide. Therefore, in the solidified body of the present invention, the inside of the biological sample and the outside of the biological sample (matrix region) in the solidified body are both adjusted so that they can be in a good vitrified state.

[0088] As a result, in the present invention, water does not form ice crystals in the solid frozen material containing the biological sample obtained after freezing, and therefore the biological sample, such as cells, is not destroyed by ice crystals and is preserved with a high viability.

[0089] In the solidified body of the present invention, ice crystals are not formed in the biological sample region, so that visible light is not blocked by ice crystals. As described above, the solvent portion and the biological sample region in the solidified body have almost the same transmittance of visible light, and even when observed under a microscope, the brightness difference between the solvent portion and the biological sample region is 3 or less in the Munsell color system. Therefore, it is easy to confirm whether the biological sample in the solidified body is alive or not by simply irradiating the frozen solid with visible light and observing it under a microscope.

[0090] The solidified body of the present invention contains a water-soluble polymer or a salt thereof at a concentration of about 0.1 w / v% or more and 20 w / v% or less. If the concentration of the water-soluble polymer is too low, the solvent portion may not be vitrified well. For example, the concentration of the water-soluble polymer or a salt thereof is preferably 1 w / v% or more, and particularly preferably 5 w / v% or more. In addition, if the concentration is higher than 20 w / v%, the viscosity may become too high, which may deteriorate the handling properties. Preferably, the concentration of the polymer or a salt thereof is 5 w / v% or more and 20 w / v% or less.

[0091] The salt of the water-soluble polymer used in the present invention may be a metal salt, a halogen salt, or a sulfate salt. The metal salt is preferably an alkali metal or an alkaline earth metal salt. The alkali metal or alkaline earth metal may be sodium, potassium, calcium, or the like. The halogen may be chlorine, bromine, or the like.

[0092] In addition, the matrix of the present invention preferably contains a low molecular weight saccharide or a salt thereof in addition to the water-soluble polymer. The amount of the low molecular weight saccharide or a salt thereof added can be appropriately adjusted to achieve the difference in brightness between the region occupied by the biological sample in the solidified body and the region occupied by the matrix in the solidified body being smaller than the desired value, and / or the temperature at which the endothermic peak appears being close to the desired temperature, as described above. For example, the low molecular weight saccharide or a salt thereof can be added so that the content ratio of the water-soluble polymer to the low molecular weight saccharide in the aqueous polymer solution is about 10:1. If the concentration of the saccharide or a salt thereof is too low, the effect of cell protection by the low molecular weight saccharide may not be sufficiently obtained. Also, even if the saccharide is added at a concentration of 1 / 10 or more of the water-soluble polymer, it is difficult to obtain further effects as a cell protection component.

[0093] In the present invention, the aqueous solvent for dissolving the water-soluble polymer to form the matrix of the solidified body is preferably water, a physiological solution, or an isotonic aqueous solution in which the salt concentration or sugar concentration is adjusted with sodium ions, potassium ions, calcium ions, etc. so as to be approximately the same as the osmotic pressure of body fluids or cell fluids. Specifically, for example, water, physiological saline, physiological saline with a buffer effect such as phosphate buffered saline (PBS), Dulbecco's phosphate buffered saline, Tris buffered saline (TBS), HEPES buffered saline, balanced salt solutions such as Hanks' balanced salt solution, Ringer's solution, lactate Ringer's solution, acetate Ringer's solution, bicarbonate Ringer's solution, etc. are exemplified, but are not limited to these. In addition, the solvent may contain other optional components such as an isotonic agent, a chelating agent, and a solubilizing agent as long as the effect of the present invention is not impaired. In this specification, the term "optional component" means a component that may or may not be contained. For example, the solvent may be a 5% glucose aqueous solution. In addition, a cell culture medium may be used as the aqueous solvent for forming the matrix of the present invention. The culture medium is not particularly limited, and examples thereof include commercially available culture media, D-MEM, E-MEM, αMEM, RPMI-1640 medium, Ham's F-12, Ham's F-10, M-199 and other basic animal cell culture media, and general culture fluids for various cells or tissues. Therefore, when freezing and preserving a biological sample using the matrix of the present invention, an aqueous solution of a water-soluble polymer may be prepared, and a biological sample such as cultured cells may be suspended in this aqueous polymer solution and frozen to produce a solidified body, or a water-soluble polymer or its salt may be added at a desired concentration to a culture fluid containing a biological sample such as a cultured cell culture fluid or a cell suspension, and frozen to produce a solidified body.

[0094] In addition, the aqueous solution in which the water-soluble polymer is dissolved may be pH-adjusted as necessary. For example, when the hydrophilic group of the monomer having a hydrophilic group is a carboxylic acid group, the aqueous solution containing the water-soluble polymer polymerized from such a monomer may be acidic. In such a case, the aqueous solution may be made neutral by adjusting the pH, which may provide a matrix more suitable for the survival of cells cryopreserved in the solidified body, and the survival rate of the cells may be improved. There is no limitation on the salt used for adjusting the pH, and any salt commonly used for adjusting the pH of an aqueous solution may be used.

[0095] According to the results of thermal analysis of the matrix of the present invention by differential scanning calorimetry (DSC), in the DSC curve of the matrix of the present invention during the temperature rise obtained under the measurement conditions of (1) to (2) below, the endothermic peak during the temperature rise has an endothermic amount of 0 J / g or 65% or less of the endothermic amount corresponding to the reference solution consisting of water, preferably 40% or less of the endothermic amount corresponding to the reference solution consisting of water.

[0096] The fact that the endothermic heat of the endothermic peak during the temperature rise process in the matrix of the present invention is smaller (less than 100%) than the corresponding endothermic heat of the reference solution made of water in the DSC measurement means that bound water and free water that do not form ice crystals remain in the frozen matrix. That is, in the aqueous solution of the water-soluble polymer forming the matrix of the present invention, the replacement of the water-soluble polymer and / or low molecular weight saccharide with water proceeds, and water molecules are trapped in the matrix of the water-soluble polymer, restricting the molecular motion of water. This promotes dehydration of water from within the cells of the biological sample contained in the matrix, and allows water to be solidified in a glassy state without crystallization. Good vitrification of the matrix in the solidified body and the inside of the biological sample contained in the solidified body is achieved. Therefore, in the solidified body of the present invention, destruction of cells due to the formation of ice crystals can be suppressed or prevented. Furthermore, in the solidified body of the present invention, not only is ice crystal formation suppressed or prevented during the cooling process, but recrystallization of water during the subsequent temperature rise process, i.e., during melting, can also be suppressed. That is, in the solidified body of the present invention, it is considered that the glassy state of the biological sample contained in the solidified body in the frozen state is stabilized. Since the glassy state is thus more stabilized, the biological sample preserved in the solidified body of the present invention exhibits a high cell protection effect without the need for the addition of protein components such as serum derived from humans or cows or serum-derived components (e.g., albumin, etc.). Therefore, the biological sample after thawing is free from concerns about infectious diseases, and is also thought to be free from the influence of lot-to-lot differences in biological preparations. It is possible to add proteins that are not contaminated by bacteria or viruses.

[0097] The solidified body of the present invention does not contain any permeating compounds in cells, so it is considered that the cytotoxicity is low when used for cryopreservation of biological samples. Furthermore, it is not necessary to increase the concentration of solutes to restrict the molecular motion of water, so it is considered that the damage to cells is low. In addition, the low molecular weight saccharide or its salt used in the present invention has a cytoprotective effect of quickly replacing the water discharged from inside the cells around the cells during freezing, so it is considered that the properties of the cells are not changed during cryopreservation. Therefore, it is considered that the biological sample is cryopreserved in the solidified body of the present invention while maintaining the properties of the cells.

[0098] In addition, unlike conventional vitrification methods, the solidified body of the present invention does not require a high cooling rate during cooling in order to reduce osmotic shock during production. Therefore, the solidified body of the present invention allows biological samples to be efficiently cryopreserved in a simple manner with reduced toxicity, and when the solidified body is thawed after cryopreservation, the thawed biological samples show a high survival rate.

[0099] According to the results of thermal analysis of the aqueous solution of the water-soluble polymer by differential scanning calorimetry (DSC), the aqueous solution of the water-soluble polymer has a glass transition temperature in the vicinity of -23°C ± 4°C. In the matrix of the water-soluble polymer of the present invention, as described above, vitrification is realized by entangling water molecules in the network of the water-soluble polymer during freezing. Therefore, a large cooling rate for cell protection during cooling, which is required in conventional vitrification methods, is not required. For this reason, after the biological sample is immersed in the aqueous solution of the polymer, the aqueous solution of the polymer is cooled to -27°C or lower, which is the glass transition temperature of the aqueous solution of the polymer. For example, the aqueous solution of the polymer containing the biological sample is placed in a freezing treatment container or the like and left in a deep freezer at -80°C, and the cells, tissues, etc. to be preserved can be stably frozen and preserved. Since a low temperature such as -150°C, which is required for the cryopreservation of normal cells, is not necessarily required, it is possible to eliminate the need for a special container for liquid nitrogen cryopreservation or the preparation of liquid nitrogen. Therefore, the operation related to the cryopreservation of biological samples can be significantly simplified. In addition, the solidified body of the present invention can suppress the recrystallization of water when the solidified body is melted, so that the solidified body of the present invention can easily and efficiently perform a series of steps of freezing, preserving, and thawing a biological sample without requiring special procedures. Of course, it is also possible to freeze and preserve a biological sample in liquid nitrogen or liquid nitrogen vapor by using an aqueous solution of a water-soluble polymer and liquid nitrogen.

[0100] Since the aqueous polymer solution used in the present invention functions as a non-permeable cryopreservation solution, the biological sample to be solidified using the aqueous polymer solution of the present invention and subjected to cryopreservation is not particularly limited. It can be used for cryopreservation of various types of cells. In addition, the origin of the cells is not particularly limited. The matrix containing the water-soluble polymer of the present invention can effectively suppress or prevent ice crystal formation and recrystallization during freezing and thawing, so it can be used well for mammalian cells with complex structures. Therefore, it can be applied to the cryopreservation of cells of various animal species, including mice, dogs, and humans. Furthermore, the matrix containing the water-soluble polymer of the present invention is known to be more damaged during freezing than general culture cells, and can be particularly suitable for cryopreservation of germ cells such as stem cells, early embryos, eggs, sperm, and fertilized eggs, which are unavoidably subject to a significant decrease in survival rate by the so-called conventional slow freezing method. In addition, the matrix containing the water-soluble polymer of the present invention does not contain chemical substances such as DMSO and ethylene glycol that can act as differentiation factors, so it can be used to preserve cells that need to be kept undifferentiated. For example, stem cells for regenerative medicine applications can be cryopreserved without the risk of differentiation.

[0101] In addition, since serum or serum-derived proteins are not added to the solidified body of the present invention, there is no contamination with bacteria or viruses. However, it is possible to add proteins that are not contaminated by bacteria or viruses. In addition, it is possible to use compounds that are cell-permeable and toxic at low concentrations that do not impair cell functions.

[0102] Furthermore, since the matrix containing the water-soluble polymer of the present invention has an excellent effect of stabilizing the glassy state in a frozen state, it can also be used for cryopreservation of large cells such as oocytes and fertilized eggs, which are known to be difficult to preserve, as well as organized cell structures, tissues, and tissue-like substances, such as tissues obtained in regenerative medicine.

[0103] That is, by incorporating a biological sample selected from cells, tissues, or tissue-like substances such as membranes or aggregates in the solidified body of the present invention, a high survival rate can be achieved in cryopreservation of the biological sample. In particular, the matrix containing the water-soluble polymer of the present invention can be advantageously used in cryopreservation of mesenchymal stem cells, hematopoietic stem cells, neural stem cells, somatic stem cells such as bone marrow stem cells and germline stem cells, blood cells, endothelial cells, and the like, regardless of whether the cells are primary cells or established cells, and in particular, in cryopreservation of stem cells of primates, which are considered to have lower freeze resistance than mice, cryopreservation of tissues for transplantation, and cryopreservation of germline cells in reproductive medicine.

[0104] In addition, if the water-soluble polymer of the present invention is, for example, a water-soluble polymer that is a biological component, it is possible to melt the solidified body and use it as a solution for administering a biological sample.Furthermore, in the case of tissue or tissue-like matter, it is also possible to add a matrix containing such a water-soluble polymer of the present invention at the organization stage, and freeze it as it is to form a solidified body.This is thought to reduce problems after transplantation.In this case, the preferred water-soluble polymer for the matrix containing the water-soluble polymer of the present invention is hyaluronic acid.In particular, the hyaluronic acid has a viscosity average molecular weight of more than 3000, more preferably more than 5000, and 60000 or less, more preferably 20000 or less.

[0105] The method for producing a solidified body containing a biological sample of the present invention includes the steps of dissolving a water-soluble polymer or a salt thereof in an aqueous solvent, and preparing a polymer aqueous solution adjusted to have the properties described above, that is, such that when frozen at -80°C, the biological sample has an orthogonal projection area that is less than 1 and reduced to at least 1 / 3.5 of that in the culture solution (culture medium) before solidification, and when frozen at -80°C, when visible light is transmitted through the biological sample, the difference in brightness in the Munsell color system between the area occupied by the biological sample and the area other than the area occupied by the biological sample is 3 or less when viewed from the light exit side, and in a DSC curve during a temperature rise process obtained under the measurement conditions (1) to (2) below using a differential scanning calorimeter (DSC), no endothermic peak is observed or the temperature at which an endothermic peak is observed is greater than -1.4°C and less than 1.1°C; a step of incorporating a biological sample in the polymer aqueous solution; and a step of cooling and freezing the polymer aqueous solution containing the biological sample. Here, the DSC measurement conditions are: (1) Hold at 20°C for 1 minute, then cool to -80°C at a rate of 5°C / min, and (2) After holding at -80°C for 1 minute, increase the temperature to 20°C at a rate of 10°C / min.

[0106] Since the aqueous solution of the water-soluble polymer forming the matrix of the present invention has a glass transition temperature of about -23°C ± 4°C, and the vitrification of the matrix is ​​realized by the water molecules being entangled in the network of the water-soluble polymer during freezing, a high cooling rate is not required in the process of producing the solidified body of the present invention. Therefore, by simply immersing a biological sample in the aqueous polymer solution used in the present invention and then cooling it to -27°C or lower, which is the glass transition temperature of the aqueous polymer solution, for example, by placing the aqueous polymer solution of the present invention containing a biological sample in a freezing treatment container or the like and leaving it in a deep freezer at -80°C, cells, tissues, etc. to be preserved can be stably frozen in the solidified body while maintaining their viability, and then preserved.

[0107] However, the range of the cryopreservation temperature is not limited as long as it is −27° C. or lower. For example, the upper limit is desirably −70° C. or lower, preferably −80° C. or lower. The lower limit is desirably −196° C. or higher, preferably −150° C. or higher.

[0108] The cooling and freezing in the process for producing the solidified body of the present invention is carried out by a slow freezing method. That is, in order to produce the solidified body of the present invention, the cooling rate is preferably 10°C / min or less. More preferably, the cooling rate is about 1°C / min or less. It is believed that at such a cooling rate, the inside of the biological sample is appropriately dehydrated, the liquid in the biological sample is satisfactorily vitrified, and a high cell cryoprotection effect can be obtained.

[0109] In the solidified body of the present invention, the vitrified state is stabilized and the toxicity to the biological sample is low, so that the biological sample can be stably stored for a long period of time. In this specification, long-term stable storage means that, for example, after thawing the solidified body of the present invention, the viability of the biological sample, for example, cells, decreases by less than 10%, preferably less than 5%, after 5 months, or by less than 20%, preferably less than 10%, after 6 months, or by less than 15%, preferably less than 30%, after 12 months, based on the viability of the cells immediately before storage. In addition, in this specification, long-term stable storage means that, for example, when cells are stored in a solidified body at -80°C for a long period of time, the solidified body is thawed, and the cells are then stored at 4°C, even 24 hours after thawing, the viability decreases by less than 5%, based on the viability of the cells immediately after thawing. In the solidified body of the present invention, it is considered that cells are cryopreserved under less stressful conditions than in conventional cryopreservation methods using DMSO solution as a cryopreservation solution. Therefore, in the biological sample preserved as the solidified body of the present invention, a very high cell viability after thawing can be obtained compared to the cryopreservation method using a conventional cryopreservation liquid such as a 10% DMSO solution. Furthermore, not only immediately after the thawing of the solidified body, but also cells preserved in a refrigerator after thawing can show a high cell viability. In the solidified body of the present invention, cells can be cryopreserved stably for a long period of time without changing the properties of the cells. Therefore, it is suitable for preserving biological samples for regenerative medicine, for example. Since no special procedures or devices are required for the production and preservation of the solidified body of the present invention, the solidified body of the present invention containing a biological sample with a high viability can be easily produced, and the transportation thereof is also easy, which can facilitate the handling of the biological sample. EXAMPLES

[0110] The present invention will be specifically described based on examples, but the present invention is not limited thereto. In the following, the hyaluronic acid manufactured by Lifecore Biomedical is sodium hyaluronate, but for the sake of simplicity, it is described as "hyaluronic acid".

[0111] Water-soluble polymers that form a matrix <Preparation of test samples and sample solutions> Example 1 In a pressure-resistant vessel with a volume of 2L, polymeric hyaluronic acid (manufactured by Shanghai Easier Industrial Development Co., Ltd.) with an average molecular weight of 1 million was mixed with water in a ratio of 20:100, and subcritical processing was performed at a processing temperature of 175°C, a processing pressure of 0.89 MPa, and a processing time of 3 minutes. The subcritically processed product was then dried by freeze drying (this drying could also be performed by the spray drying method). As a result, a water-soluble polymer was obtained, which was a mixture of polymeric hyaluronic acid with a viscosity average molecular weight of about 10,000 and hyaluronic acid with a viscosity average molecular weight of 1,000.

[0112] When this water-soluble polymer was confirmed by HPLC (Fig. 12), it was considered that the test sample of Example 1 was a mixture of high molecular weight hyaluronic acid decomposition product and low molecular weight hyaluronic acid decomposition product by subcritical treatment of hyaluronic acid, so high molecular weight hyaluronic acid was precipitated in ethanol, low molecular weight hyaluronic acid was fractionated on the supernatant side, and this fractionated supernatant was reanalyzed by HPLC.Since it was roughly consistent with the HPLC peaks (Fig. 11A-C) of hyaluronic acid of Production Examples 1-3 described later, the viscosity average molecular weight of the low molecular weight hyaluronic acid component obtained by this Example 1 was estimated to be 1000.

[0113] The intrinsic viscosity of the high molecular weight hyaluronic acid was 0.49 dL / g, and the viscosity average molecular weight was 10,000.

[0114] The test sample solution of Example 1 was obtained by dissolving 1 g of the test sample of Example 1 in 10 mL of α-MEM medium (manufactured by Gibco, product number C1257-1500BT, the solvent is water) as a solvent (i.e., the concentration of the hyaluronic acid sample in the test sample solution is 10 w / v%). Including this Example 1, in the examples, production examples and comparative examples of the present invention, α-MEM medium is used as the solvent, but ultrapure water may be used as the solvent instead of α-MEM medium. In the DSC measurement described later, the solvent is ultrapure water instead of α-MEM. Note that each test sample obtained in the following examples was prepared to a predetermined concentration using an appropriate solvent and used in the tests for each evaluation described later.

[0115] Manufacturing Example 1 The same procedure as in Example 1 was carried out except that the subcritical treatment was carried out for 7 minutes, to obtain a test sample which was a hyaluronic acid fragment having a viscosity average molecular weight of 1000. The intrinsic viscosity was 0.08 dL / g.

[0116] Manufacturing Example 2 The same procedure as in Example 1 was carried out except that the subcritical treatment was carried out for 5 minutes, to obtain a test sample which was a hyaluronic acid fragment having a viscosity average molecular weight of 2000. The intrinsic viscosity was 0.14 dL / g.

[0117] Manufacturing Example 3 The same procedure as in Example 1 was carried out except that the subcritical treatment was carried out for 4 minutes, to obtain a test sample which was a hyaluronic acid fragment having a viscosity average molecular weight of 3000. The intrinsic viscosity was 0.19 dL / g.

[0118] Comparative Example 1 DMSO (Nacalai Tesque, Inc., cell culture grade) was used as a test sample. 1 mL of this test sample was dissolved in 10 mL of α-MEM medium (Gibco, product number C1257-1500BT, the solvent is water) to obtain a test sample solution of Comparative Example 1 (i.e., the DMSO concentration of the test sample in the test sample solution was 10 w / v%).

[0119] Comparative Example 2 The αMEM medium (Gibco, product number C1257-1500BT, the solvent is water) used as a solvent was used as a test sample.

[0120] Comparative Example 3 1 g of gelatin (viscosity average molecular weight 315000, manufactured by Nitta Gelatin Co., Ltd.) was dissolved in 10 mL of αMEM medium (manufactured by Gibco, product number C1257-1500BT, the solvent is water) as a solvent to obtain a test sample solution of Comparative Example 3 (i.e., the gelatin concentration of the test sample in the test polymer aqueous solution was 10 w / v%). The intrinsic viscosity was 0.50 dL / g.

[0121] Comparative Example 4 1g of high molecular weight hyaluronic acid (manufactured by Shanghai Easier Industrial Development Co., Ltd.) with viscosity average molecular weight of 1,000,000 is dissolved in 100mL of αMEM medium (manufactured by Gibco, product number C1257-1500BT, solvent is water) as solvent, to obtain the test sample solution of Comparative Example 4 (i.e., the concentration of the hyaluronic acid of the test sample in the test sample solution is 1w / v%). The intrinsic viscosity is 17.2dL / g.

[0122] Comparative Example 5 Hyaluronic acid (lifecore biomedical; powder) with viscosity average molecular weight of 15000 was used as the test sample. 1g of this test sample was dissolved in 10mL of αMEM medium (Gibco, product number C1257-1500BT, solvent is water) to obtain the test sample solution of Comparative Example 5 (i.e., the concentration of hyaluronic acid of the test sample in the test sample solution is 10w / v%). The intrinsic viscosity was 0.65dL / g.

[0123] Comparative Example 6 Chondroitin sulfate sodium salt A (manufactured by Sigma) with a viscosity average molecular weight of 23,000 was used as the test sample. 1 g of this test sample was dissolved in 10 mL of α-MEM medium (manufactured by Gibco, product number C1257-1500BT, the solvent is water) to obtain a test sample solution of Comparative Example 6 (i.e., the chondroitin sulfate concentration of the test sample in the test sample solution was 10 w / v%). The intrinsic viscosity was 0.97 dL / g.

[0124] Comparative Example 7 The test sample of Production Example 1 (a hyaluronic acid fragment sample with a viscosity average molecular weight of 1000) was added in an amount of 1 w / v% to carboxypolylysine (viscosity average molecular weight 13400: Bioverde Co., Ltd., CryoScarless DMSO free) with 60% amino groups carboxylated, to prepare a test sample solution of Comparative Example 7. The intrinsic viscosity was 0.11 dL / g.

[0125] Comparative Example 8 The test sample used was fructan derived from shallots. The fructan was obtained by extraction and purification according to Example 2 of JP 2012-235728 A as follows.

[0126] Approximately 1 kg of dried shallots as raw material was crushed and mixed with water for extraction in which 15 g of calcium hydroxide was suspended. Extraction was performed at room temperature for 1 hour, followed by heating extraction at 95°C for 1 hour, and then heating extraction at 60°C overnight. Activated carbon was added to the extract for deodorization, and then it was filtered through diatomaceous earth to remove residue and activated carbon. The obtained extract was passed through an ultrafiltration membrane to purify fructans.

[0127] The purified liquid was once heat-sterilized, and then decolorized again by adding activated carbon. The purified liquid was sterilized by heating at 85°C for 1 hour, freeze-dried, and powdered to obtain 400 g of purified fructan powder.

[0128] The viscosity average molecular weight of the resulting purified fructan powder was measured and found to be 12,000.

[0129] 1 g of this fructan powder was dissolved in 10 mL of α-MEM medium as a solvent to obtain a test sample solution of Comparative Example 8 (i.e., the test sample fructan concentration in the test sample solution was 10 w / v%). The intrinsic viscosity was 0.11 dL / g.

[0130] Comparative Example 9 Pullulan (Tokyo Chemical Industry Co., Ltd.) with a viscosity average molecular weight of 373,000 was used as a test sample. 1 g of this test sample was dissolved in 10 mL of αMEM medium (Gibco, product number C1257-1500BT, solvent is water) to obtain a test sample solution of Comparative Example 9 (i.e., the hyaluronic acid concentration of the test sample in the test sample solution is 10 w / v%). The intrinsic viscosity was 0.55 dL / g.

[0131] Comparative Example 10 The test sample of Comparative Example 5 (hyaluronic acid with viscosity average molecular weight of 15000) 1g is dissolved in αMEM medium (Gibco, product number C1257-1500BT, solvent is water) 10mL to obtain an aqueous solution with hyaluronic acid concentration of 10w / v%, and the test sample of Preparation Example 2 (hyaluronic acid fragment sample with viscosity average molecular weight of 2000) is added in a final concentration of 1w / v% to obtain the test sample solution of Comparative Example 10. The intrinsic viscosity is 0.47dL / g.

[0132] Example 2 The test sample of Comparative Example 5 (hyaluronic acid with viscosity average molecular weight of 15000) 1g was dissolved in αMEM medium (Gibco, product number C1257-1500BT, solvent is water) 10mL to obtain a test sample solution with a hyaluronic acid concentration of 10w / v%, and the test sample of Production Example 1 (hyaluronic acid fragment sample with viscosity average molecular weight of 1000) was added in a final concentration of 1w / v%. The pH of the obtained aqueous solution was adjusted to neutral using 10mM Tris-HCl to obtain the test sample solution of Example 2. The intrinsic viscosity was 0.65dL / g.

[0133] Example 3 The test sample of Comparative Example 9 (pullulan with viscosity average molecular weight of 373000) 1g is dissolved in αMEM medium (Gibco, product number C1257-1500BT, solvent is water) 10mL to obtain a test sample solution with a pullulan concentration of 10w / v%, and the test sample of Preparation Example 1 (hyaluronic acid fragment sample with viscosity average molecular weight of 1000) is added to the test sample solution with a final concentration of 1w / v% to obtain the test sample solution of Example 3. The intrinsic viscosity is 0.55dL / g.

[0134] Example 4 The test sample of Comparative Example 9 (pullulan with a viscosity average molecular weight of 373,000) was dissolved in 10 mL of αMEM medium (Gibco, product number C1257-1500BT, solvent is water) to obtain a test sample solution with a pullulan concentration of 10 w / v%, to which the test sample of Preparation Example 1 (hyaluronic acid fragment sample with a viscosity average molecular weight of 1000) was added at a final concentration of 5 w / v%. The pH of the obtained aqueous solution was adjusted to neutral using 10 mM Tris-HCl to obtain the test sample solution of Example 4. The intrinsic viscosity was 0.55 dL / g.

[0135] Example 5 In a pressure-resistant vessel with a volume of 2L, polymeric hyaluronic acid (manufactured by Shanghai Easier Industrial Development Co., Ltd.) with an average molecular weight of 1 million was mixed with water in a ratio of 20:100, and subcritical processing was carried out at a processing temperature of 175°C, a processing pressure of 0.89MPa, and a processing time of 3.5 minutes. The subcritically processed product was then dried by freeze-drying or spray-drying. As a result, a hyaluronic acid sample with a viscosity average molecular weight of approximately 6000 was obtained.

[0136] 1g of this hyaluronic acid is dissolved in 10mL of αMEM medium (Gibco, product number C1257-1500BT, solvent is water) to obtain a test sample solution with a hyaluronic acid concentration of 10w / v%, and sucrose (Nacalai Tesque, molecular weight (same value as viscosity average molecular weight) is 342) and glucuronic acid (Fujifilm Wako Pure Chemical, molecular weight (simulated to viscosity average molecular weight) 194) are added at a final concentration of 1w / v% to obtain a test cryopreservation solution of Example 5. The intrinsic viscosity was 0.32dL / g.

[0137] <Test Example 1: Cryopreservation of primary human mesenchymal stem cells in a solidified body using a test sample solution and evaluation of the preservation effect> Cultured primary human mesenchymal stem cells (Lonza PT2501) were added at a concentration of 1 × 10 6 The antibodies were suspended in the test sample solutions (serum-free) of Examples 1 and 5 and Comparative Examples 1, 2, 4, 5, 7 and 8 at a concentration of 100000000000 / mL.

[0138] The cell suspension containing each test sample solution was then frozen in a slow cell freezer (Nalgene (registered trademark) Mr. Frosty) in a -80°C freezer to obtain a solidified body. The solidified body was stored at -80°C for 7 days and then rapidly thawed in a 37°C warm bath. The cell suspension containing each test sample solution after thawing was evaluated for cell viability by trypan blue staining immediately after thawing. The results are shown in Figure 1 and Table 1 (the results of Example 5 are only in Table 1).

[0139] FIG. 1 shows the cell viability after thawing of cells cryopreserved in a medium without cryopreservation solution, i.e., in a solidified body containing the test sample solution of Comparative Example 2, or in a solidified body containing the test sample solutions of Example 1 and Comparative Examples 1, 4, 5, 7 and 8. As shown in FIG. 1, in Example 1, that is, in the solidified body containing the test sample solution of Example 1, in which the hyaluronic acid sample obtained by subcritical treatment of hyaluronic acid has a viscosity average molecular weight of about 10,000, and further contains a hyaluronic acid cleavage product having a viscosity average molecular weight of 1000, i.e., a molecular weight smaller than 10,000, is a water-soluble polymer, and the intrinsic viscosity of the aqueous solution is 0.49 dL / g, a remarkably high preservation effect exceeding 90% was obtained. This preservation effect was even higher than that of Comparative Example 1, which contains DMSO, a commonly used cryopreservation agent, as a cryopreservation agent. It can be seen that freezing in the solidified body of the present invention is an excellent cryopreservation with low cytotoxicity.

[0140] In the frozen solidified body of Example 1, no endothermic peak was observed in the DSC measurement during the temperature rise process (see Test Example 2 below), and it is presumed that the water molecules do not form ice crystals, but are free water or bound water adsorbed or entangled by hyaluronic acid molecular chains. In addition, since the brightness difference between the solvent matrix region and the cell region of this frozen solidified body is small at 2 (see Test Example 8 below), it is considered that the existence state of water molecules in the solvent matrix region and the cell region is similar, and ice crystals are not formed inside the cells. Furthermore, since the area of ​​the cells when the test sample solution is solidified at -80°C is shrunk to 38% of the area of ​​the cells in the culture solution (culture medium) before solidification (see Test Example 9 below), it is considered that hyaluronic acid does not enter the cells, and water molecules move out of the cells due to the osmotic pressure difference. The water molecules that move out of cells are thought to be replaced with low molecular weight hyaluronic acid or high molecular weight hyaluronic acid, and do not cause problems such as destruction of cell tissue by remaining around cells and forming ice crystals, and hyaluronic acid does not enter cells and harm cells. Therefore, unlike DMSO in Comparative Example 1, it has low cytotoxicity and does not form ice crystals inside or around cells, so it is also excellent in the cryopreservation effect of cells.

[0141] In the solidified body containing the test sample solution of Comparative Example 4, which contains high molecular weight hyaluronic acid with a molecular weight of 1,000,000 as a test sample and has a high intrinsic viscosity of 17.2 dL / g, almost no cell protection effect was observed. In the frozen solidified body of Comparative Example 4, no endothermic peak was confirmed in the DSC measurement during the temperature rise process (see Test Example 2 below), but the frozen solidified cells did not shrink, water molecules remained in the cells, and the brightness difference between the solvent matrix region and the cell region of the frozen solidified body was large at 4 (see Test Example 8 below), the cell region was dark, and it is considered that the water molecules in the cells formed ice crystals. For this reason, it is presumed that the ice crystals destroyed the cells, and the cell preservation effect was not observed.

[0142] In Comparative Example 2, which did not contain a cryopreservative, the cell viability was approximately 0%.

[0143] In Comparative Example 7, which contains carboxypolylysine as a test sample and has a low intrinsic viscosity of 0.11 dL / g, the cell protection effect was not as good as that of Example 1 or Comparative Example 1, which uses DMSO as a cryoprotectant. In Comparative Example 7, the temperature at which the endothermic peak appears in the DSC measurement during the temperature rise process is low at -9.66°C (see Test Example 2 below), and it is considered that the freezing speed of water is slow and ice crystals are formed. In addition, since the brightness difference between the solvent matrix region and the cell region is small (see Test Example 8 below), it is presumed that the ice crystal formation state is similar between the solvent matrix region and the cell region, and ice crystals are formed inside the cells. Also, since the area of ​​the cells after freezing is larger than the area in the culture solution (culture medium) (see Test Example 9 below), it is considered that polylysine has penetrated into the cells or the cells have expanded due to ice crystals. It is presumed that the cells are damaged and sufficient preservation effect cannot be obtained.

[0144] As for the fructan of Comparative Example 8, the temperature at which the endothermic peak appeared was low at -2°C (see Test Example 2 below), which suggests that the freezing rate of water was slow and ice crystals were likely to form easily, and since the cells were larger than the area of ​​the culture solution (culture medium) and bursting was observed (see Test Example 9 below), it is thought that the fructan penetrated into the cells. In addition, since the brightness difference between the solvent matrix region and the cell region after freezing and solidifying was large at 5, and the cell region was dark (see Test Example 8 below), it is presumed that ice crystals were formed within the cells, and it is thought that a sufficient preservation effect was not obtained.

[0145] In this way, by adjusting the temperature at which an endothermic peak does not appear in the DSC measurement during the heating process or by adjusting the temperature at which it appears so that it appears near 0.7°C (-1.4°C to 1.1°C), which is the endothermic peak of water, it is possible to suppress the formation of ice crystals in the solvent matrix and reduce the brightness difference between the solvent matrix region and the cell region, thereby approximating the ice crystal formation states of the two.It is also possible to solidify the cells in such a way that they shrink, thereby suppressing the entry of water-soluble polymers into the cells, reducing the number of water molecules inside the cells, and preventing the formation of ice crystals inside the cells, thereby achieving excellent cell cryopreservation effects.

[0146] Furthermore, the frozen solidified material of the present invention has the effect of making it possible to estimate whether or not the cells have been cryopreserved satisfactorily by DSC measurement, brightness measurement, and measurement of the orthogonal projected area of ​​the cells, without thawing.

[0147] Furthermore, it can be seen from Example 5 that glucuronic acid and sucrose also have the function of adjusting the endothermic peak to around 0.7°C (the endothermic peak of hyaluronic acid with a viscosity average molecular weight of approximately 6000 is -1.4°C).

[0148] [Table 1]

[0149] In addition, since the solidified material of the present invention showed a high cell preservation effect even when produced using a culture medium such as αMEM medium instead of water as the aqueous solvent for dissolving the water-soluble polymer, the solidified material of the present invention can be produced by adding the polymer aqueous solution directly to the cell culture medium, suspending the cells, and then freezing, and can be preserved as is. It is believed that there is no need to centrifuge the cells to be preserved, and a higher cell survival rate and maintenance of cell properties are possible.

[0150] <Test Example 2: Analysis of each test sample solution by differential scanning calorimeter> The solvent of each test sample solution in Examples 1 to 5, Comparative Examples 1 to 10, and Production Examples 1 to 3 was changed from αMEM medium to ultrapure water to prepare samples for differential scanning calorimetry. Each sample was scanned with a differential scanning calorimeter (DSC) as follows. (1) After holding at 20°C for 1 minute, cool to -80°C at any speed. (2) After holding at -80°C for 1 minute, increase the temperature to 20°C at a rate of 10°C / min.

[0151] The DSC curves during the temperature rise obtained under the above DSC measurement conditions for Example 1, Comparative Example 5, and ultrapure water (Comparative Example 2) are shown in Figure 2A. Figure 2B is an enlarged view of Figure 2A near the glass transition temperature. Figures 3A to 3C show the DSC curves for Example 1, Comparative Example 1, and ultrapure water (Comparative Example 2).

[0152] In addition, the temperature at which an endothermic peak presumably due to water melting was observed in the DSC curve during the temperature rise of each test sample solution, and the endothermic amount (amount of heat absorbed during temperature rise) of the endothermic peak observed in the DSC curve during the temperature rise were analyzed. The results are shown in Table 1. In Table 1, the endothermic amount of the endothermic peak is shown as a percentage (%) relative to the calorific value of 112.4 J / g measured in ultrapure water (Comparative Example 2; reference solution) taken as 100.

[0153] As shown in Figures 2A and 2B, in Comparative Example 2 in which the test sample was ultrapure water (i.e., a sample in which the test sample was ultrapure water), only the ice crystal melting peak of free water was observed (Figure 2A). In Comparative Example 5 in which the test sample was hyaluronic acid with a viscosity average molecular weight of 15,000, a shift in the ice crystal melting peak and a drop in the freezing point were observed compared to Comparative Example 2 (Figure 2A), and a glass transition was confirmed near -20°C (Figure 2B). On the other hand, in the test sample of Example 1, which contains hyaluronic acid with a viscosity average molecular weight of about 10,000 as well as a scission product of hyaluronic acid (low molecular weight hyaluronic acid with a viscosity average molecular weight of 1000), the ice crystal melting peak was extremely small and almost not observed (Figure 2A), and only a glass transition was confirmed near -23°C ± 4°C (Figure 2B). These results show that in the solidified body of Example 1, water exists in the matrix in an unfrozen state (free water) or in a state trapped by polymers (bound water), and that recrystallization of water is suppressed upon melting, which are significantly advantageous effects of the solidified body of the present invention.

[0154] Furthermore, as shown in FIG. 3A, in Comparative Example 2 in which the test sample was ultrapure water, a very large heat of heat associated with ice crystal formation was observed during the temperature drop process. Also, a large amount of heat of fusion associated with ice crystal melting was observed during the temperature rise process. In Comparative Example 1 in which the test sample was DMSO, as shown in FIG. 3B, only a small peak associated with ice crystal formation was observed, and almost no peak associated with ice crystal melting was observed. This indicates that the cryopreservation solution containing the test sample (DMSO) of Comparative Example 1 is close to a vitrified state in the frozen state. In the polymer aqueous solution of the test sample of Example 1 (hyaluronic acid with a viscosity average molecular weight of 10,000 containing a cleavage product of hyaluronic acid), as shown in FIG. 3C, almost no melting peak was observed, and the peak associated with ice crystal formation was much smaller than the peak observed in Comparative Example 1. Therefore, it is considered that almost no ice crystals are formed in the solidified body containing the test sample of Example 1, and the state is in an extremely good vitrified state.

[0155] In addition, the temperature at which endothermic peak is observed (endothermic peak temperature) is -1.4°C in Comparative Example 5 (test sample is hyaluronic acid with viscosity average molecular weight of 15000), but -0.4°C in Example 2, which is made by mixing Comparative Example 5 with hyaluronic acid fragments of Preparation Example 1 with viscosity average molecular weight of 1000 or less, and is close to the endothermic peak appearance temperature of pure water, 0.7°C. The endothermic peak temperature of Preparation Example 1 is -8.1°C, and if it is added to a water-soluble polymer with a lower endothermic peak appearance temperature than pure water, it is expected that the endothermic peak appearance temperature will be further reduced, but conversely, the endothermic peak appearance temperature will rise and be close to the endothermic peak appearance temperature of pure water, or it can be adjusted so that endothermic peak or exothermic peak does not appear.

[0156] On the other hand, the endothermic peak appearance temperature of Comparative Example 9 (the test sample was pullulan with a viscosity average molecular weight of 373,000) was 1.49° C., which was higher than the endothermic peak appearance temperature of pure water, 0.7° C. When this Comparative Example 9 was mixed with Production Example 1 (endothermic peak appearance temperature: −8.1° C.) (Examples 3 and 4), the endothermic peak appearance temperature was not increased but decreased to 0.83° C., which is close to the endothermic peak appearance temperature of pure water, 0.7° C.

[0157] In other words, it was revealed that when hyaluronic acid with a molecular weight of 1000 or less is mixed with a water-soluble polymer whose endothermic peak appears at a lower temperature than pure water, the peak appears temperature of the polymer aqueous solution rises and is closer to that of pure water, and when hyaluronic acid with a molecular weight of about 1000 is mixed with a water-soluble polymer whose endothermic peak appears at a higher temperature than pure water, the peak appears temperature of the polymer aqueous solution falls and is closer to that of pure water.

[0158] In contrast, the endothermic peak temperature of the hyaluronic acid fragments having a viscosity average molecular weight of 2000 or less in Production Example 2 was -0.3°C, as shown in Table 1. The endothermic peak temperature of Comparative Example 10, in which the low molecular weight sample of Production Example 2 was mixed with Comparative Example 5 (endothermic peak appearance temperature of -1.4°C), was lowered to -1.6°C.

[0159] This result shows that by using a low molecular weight saccharide or its salt, particularly preferably a low molecular weight saccharide having a viscosity average molecular weight of 1000 or less, the endothermic peak temperature of the polymer aqueous solution can be adjusted to be around the endothermic peak temperature of pure water, 0.7° C. When sucrose, trehalose, or glucuronic acid was used as the low molecular weight saccharide or its salt having a viscosity average molecular weight of 1000 or less, an effect similar to that of the sample in Production Example 1 on the endothermic peak temperature was observed.

[0160] In addition, the endothermic heat amounts of the endothermic peaks in the temperature rise process of the test sample solutions of Examples 1 to 5 were smaller than the corresponding endothermic heat amount of the reference solution (Comparative Example 2) made of water, being 65% or less. It is understood that in the solidified body of the present invention, water is solidified in a glassy state without being crystallized.

[0161] The endothermic peak temperatures of the test sample solutions in Examples 1 to 5 are near the endothermic peak temperature of water, 0.7°C, i.e., they behave similarly to pure water, and the endothermic amounts of the endothermic peaks are smaller than those of the endothermic peaks observed during the temperature rise of water, which indicates that bound water and free water that do not form ice crystals remain in the matrix of the frozen solidified body of the present invention. It is believed that the water-soluble polymer used in the present invention traps water molecules in its matrix during freezing, thereby realizing vitrification.

[0162] <Test Example 3: Evaluation of long-term preservation effect of cryopreservation in solidified body using test sample solution of primary human mesenchymal stem cells> Cultured primary human mesenchymal stem cells (Lonza PT2501) were added at a concentration of 1 × 10 6 The cells were suspended in the test sample solutions (serum-free) of Example 1 and Comparative Example 1 at a concentration of 1000 / mL. The cell suspensions containing each test sample solution were then frozen in a slow cell freezer (Nalgene (registered trademark) Mr. Frosty) in a -80°C freezer to obtain solidified bodies. The solidified bodies were stored at -80°C for up to 12 months, and then removed at the designated storage period and rapidly thawed in a 37°C warm bath. The cell viability of the cell suspensions containing each test sample solution after thawing was evaluated by trypan blue staining immediately after thawing. The results are shown in Figure 4A. The solidified bodies frozen and stored at -80°C for 3 months were thawed and then stored at 4°C for one day or one week. The cell viability of the cell suspensions after storage at 4°C was evaluated by trypan blue staining. The cell viability after storage at 4°C was calculated by setting the cell viability immediately after thawing (i.e., immediately before storage) as 100%. The results are shown in Figure 4B.

[0163] From the results shown in FIG. 4A, it can be seen that the cells frozen in the solidified body of the present invention show a high cell viability of 95% or more, which remains almost unchanged even after 5 months of storage. On the other hand, in the case of cryopreservation using the sample solution containing the test sample (DMSO) of Comparative Example 1, a decrease in cell viability was already observed after 2 months of cryopreservation. And, it can be seen that after 3 months, the cell viability in the cryopreservation of Comparative Example 1 is below 50%. This result is in contrast to the solidified body of the present invention, in which high cell viability is still maintained even after 3 months. After 6 months of cryopreservation, the cell viability decreased by less than 10% in the case of cryopreservation in the solidified body of the present invention, while the cell viability decreased to about 25% in the case of cryopreservation using the sample solution of Comparative Example 1. Furthermore, in the case of cryopreservation in the solidified body of the present invention, the cell viability was still high even after 12 months of cryopreservation, and the decrease in cell viability was only less than 15%.

[0164] Therefore, it is evident that the solidified body of the present invention enables cells to be cryopreserved stably for a long period of time with a high cell survival rate.

[0165] In addition, when cells stored for a long period at -80°C were thawed and then stored at 4°C, the cell viability after one day of storage at 4°C was nearly 100% of the cell viability immediately before storage when the solidified body of the present invention was used, whereas in Comparative Example 1, it had decreased to about 60%. In the cells cryopreserved in the solidified body of the present invention, even after one week of storage at 4°C, a cell viability of 40% or more was still observed. This indicates that the cells that survived after thawing in the solidified body of the present invention were essentially cells that were normally proliferating, and that the matrix in the solidified body of the present invention did not damage the cells during storage, confirming that the matrix in the solidified body of the present invention has a very excellent cell preservation effect.

[0166] <Test Example 4: Evaluation of cell properties after cryopreservation in a solidified body using a test sample solution of primary human mesenchymal stem cells> Cultured primary human mesenchymal stem cells (Lonza PT2501) were added at a concentration of 1 × 106 The cells were suspended in the test sample solutions (serum-free) of Example 1 and Comparative Example 1 at a concentration of 1000 cells / mL. The cell suspensions containing each test sample solution were then frozen in a slow cell freezer (Nalgene (registered trademark) Mr. Frosty) in a -80°C freezer to obtain solidified bodies. The solidified bodies were stored at -80°C for 6 months. After 6 months, each solidified body was quickly thawed in a 37°C warm bath, washed with αMEM, and then plated at 2.5 × 10 cells / mL in a 6-well plate. 4 After 4 days, the HGF and IL-10 concentrations in the culture medium were quantified. The quantification of HGF and IL-10 was performed using dedicated kits (Quantikine (registered trademark) ELISA Human HGF, catalog number DHG00, manufactured by R&D) and Quantikine (registered trademark) ELISA Human IL-10, catalog number D100B, manufactured by R&D), respectively, according to the procedure in the kit instructions. The results are shown in Figures 5A and 5B.

[0167] As shown in Fig. 5A, in the case of cryopreservation in the presence of the sample solution of Comparative Example 1 containing DMSO as a cryopreservative, the HGF production in cells after thawing was high. On the other hand, in the case of the solidified body of the present invention of Example 1 containing hyaluronic acid with a viscosity average molecular weight of 10000 including hyaluronic acid cleavage products, the HGF production in cells after thawing was low, being 1 / 3 or less than that of Comparative Example 1. The results in the presence of DMSO show that cells were in a stressed state when preserved in the presence of DMSO. Since such high HGF production is not observed in cell preservation using the solidified body of the present invention, it can be seen that cells are stably protected in the solidified body of the present invention.

[0168] 5B, the amount of IL-10 produced was high in the cells cryopreserved in the solidified material of Example 1, and was very low in the cells cryopreserved using the test sample solution of Comparative Example 1. This result shows that the solidified material of the present invention can satisfactorily cryopreserve cells while maintaining their functions.

[0169] Since the solidified body of the present invention does not contain compounds having cytotoxicity such as DMSO and ethylene glycol, cryopreservation in the solidified body of the present invention has the remarkable effect of enabling cryopreservation while maintaining the properties of a biological sample without exposing the biological sample to a stressful condition, unlike conventional cryopreservation solutions.

[0170] In addition, because serum or serum-derived proteins are not added, there is no contamination with bacteria or viruses. However, it is possible to add proteins that are not contaminated by bacteria or viruses. In addition, it is possible to use compounds that are cell-permeable and toxic at low concentrations that do not impair cell function.

[0171] <Test Example 5: Evaluation of cell properties (undifferentiated state) after cryopreservation in a solidified body using a test sample solution of primary human mesenchymal stem cells> Cultured primary human mesenchymal stem cells (Lonza PT2501) were added at a concentration of 1 × 10 6 The cells were suspended in the test sample solutions (serum-free) of Example 1 and Comparative Example 1 at a concentration of 1000 / mL. The cell suspensions containing each test sample solution were then frozen in a slow cell freezer (Nalgene (registered trademark) Mr. Frosty) in a -80°C freezer to obtain solidified bodies. The solidified bodies were stored at -80°C for 6 months. After 6 months, each solidified body was removed and quickly thawed in a 37°C warm bath. The expression intensities of CD90, CD44, and CD105 in the cell suspensions containing each test sample solution after thawing were analyzed by flow cytometry. The results are shown in Figure 6.

[0172] CD90, CD44 and CD105 are typical surface proteins expressed in undifferentiated mesenchymal stem cells and are used as undifferentiated markers for mesenchymal stem cells. As shown in FIG. 6, the expression of all undifferentiated biomarkers, CD90, CD44 and CD105, was higher in the cells cryopreserved in the solidified body of Example 1 than in the cells cryopreserved in the test sample solution of Comparative Example 1. Therefore, it can be seen that the cells cryopreserved in the solidified body of Example 1 maintain the expression of undifferentiated markers. That is, the cells can maintain an undifferentiated state in the solidified body of Example 1. It can be seen that the cryopreservation using the solidified body of the present invention can reduce the influence on the differentiated state seen in the case of storage in the test aqueous solution of Comparative Example 1.

[0173] These results demonstrate that the cryopreservation in the solidified body of the present invention can be suitably applied to the cryopreservation of stem cells, for which it is important to cryopreserve them in an undifferentiated state.

[0174] <Test Example 6: Evaluation of cell viability in solidified bodies containing various samples> Cultured primary canine mesenchymal stem cells (cyagen C160) were added at 1 × 10 6 The cells were suspended in the test sample solutions (serum-free) of Examples 1 to 4 and Comparative Examples 3, 6, 9 and 10 at a concentration of 1000 / mL (however, the concentration of the hyaluronic acid sample in the test sample solution of Example 1 was 20 w / v%). Then, the cell suspensions containing each test sample solution were frozen in a slow cell freezer (Nalgene (registered trademark) Mr. Frosty) in a -80°C freezer to obtain solidified bodies. After storing each solidified body for one day, each solidified body was taken out and quickly thawed in a 37°C warm bath. The cell viability of the cell suspensions containing each test sample solution after thawing was evaluated by trypan blue staining. The results are shown in Table 1.

[0175] From the results of cell viability shown in Table 1 together with the results of Test Example 1, it can be seen that the water-soluble polymer in the present invention is not limited to hyaluronic acid, and even if it is another water-soluble polymer, it will show high cell protection effect as long as the polymer aqueous solution has a predetermined endothermic peak temperature. In addition, from the results of Comparative Example 9 and Examples 3 and 4 (Comparative Example 9 to which Production Example 1 is added), it was found that by combining a water-soluble polymer with a sugar or its salt having a smaller molecular weight, the matrix of the solidified body shows good cell protection effect. This is presumably due to the fact that, as shown in the results of Test Example 2, the endothermic peak temperature of the sample solution can be adjusted to the endothermic peak temperature of pure water, 0.7 ° C, by adding a low molecular sugar or its salt to the polymer aqueous solution. Comparative Example 10 is a test sample solution obtained by adding the low molecular weight saccharides (hyaluronic acid fragment sample with viscosity average molecular weight of 2000) of Production Example 2 to the polymer aqueous solution of hyaluronic acid with viscosity average molecular weight of 15000 (Comparative Example 5). As shown in the results of Test Example 2, the endothermic peak temperature of the DSC curve is -1.6°C, which is lower than the endothermic peak temperature (-1.4°C) of Comparative Example 5, and is far from the endothermic peak appearance temperature of pure water, 0.7°C. As a result, the cell viability rate was not as high as that of the Examples. From these results, it was found that a higher cell viability rate can be obtained by mixing low molecular weight saccharides or their salts into the polymer aqueous solution and adjusting the endothermic peak temperature of the test sample solution to a desired range.

[0176] In addition, when the test sample solution prepared by adding saccharides or their salts was acidic, a good cell protection effect was obtained by neutralizing the test sample solution by pH adjustment. It is considered that the pH adjustment provides more suitable conditions for cell survival. In order for the added low molecular weight saccharides or their salts to act as cell protective components and further improve the cell survival rate of cells after cryopreservation, it was necessary to add low molecular weight saccharides or their salts to the polymer aqueous solution in an amount of 1 to 5 w / v% relative to the water-soluble polymer. On the other hand, even if the amount of the added low molecular weight saccharides or their salts was more than 10 w / v% relative to the water-soluble polymer, no further effect on the improvement of cell survival rate was observed.

[0177] Also, from Table 1, it can be seen that the intrinsic viscosity (η) of the test sample solution is more preferably in the range of about 0.20 dL / g or more and 0.95 dL / g or less in order to increase the cell viability. When the intrinsic viscosity (η) is within the above-mentioned predetermined range, it is considered that the matrix containing the polymer solution helps the discharge of water molecules from the biological sample, and the discharged water molecules can be efficiently replaced with polymers and / or low molecular weight sugars around the biological sample. Also, from Table 1, it can be seen that when the endothermic peak temperature of the DSC curve is -1.4°C or less and greater than 1.1°C, the cell viability after frozen storage decreases. In other words, it is considered that the endothermic peak temperature is greater than -1.4°C and less than 1.1°C, which indicates that the polymer solution can retain water molecules in the polymer matrix when frozen.

[0178] Furthermore, the results of Test Example 6 demonstrated that the solidified material of the present invention exhibited a favorable cryoprotective effect not only on human but also on canine mesenchymal stem cells.

[0179] <Test Example 7: Evaluation of cells in solidified bodies (evaluation of intracellular vitrification state)> Cultured primary canine mesenchymal stem cells (cyagen C160) were added at 1 × 10 6The cells were suspended in the test sample solutions (serum-free) of Example 1 and Comparative Example 1 at a concentration of 1000000000000 / mL. As a control, a control suspension was prepared in the test sample solution of Comparative Example 2 consisting of α-MEM medium without a cryopreservative. Then, 5 μL of the cell suspension and the control suspension containing each test sample solution were added to a hard glass sample placement plate (16φ×0.12 mm), covered with a hard glass cover glass (12φ×0.12 mm), cooled to −80° C. at 5° C. / min on a linKam microscope cooling stage (THMS600), and images of the solidified bodies were taken at −80° C. with a transmitted light microscope (Olympus BX53). The results are shown in FIGS. 7A-C.

[0180] FIG. 7A shows the results for the control suspension, and it can be seen that in the medium alone, ice crystals are generated within the cells in the solidified body, causing light to be diffusely reflected, causing the cells to turn dark. FIG. 7B shows the results for Comparative Example 1, in which DMSO is used as the test sample. In FIG. 7B, it can be seen that the cells also turn dark, and that minute ice crystals have formed. FIG. 7C shows the results for the solidified body of Example 1. It can be seen that the cells turn bright, and that the inside of the cells in the solidified body has vitrified to an amorphous state.

[0181] From this result, it can be seen that the solidified body of the present invention freezes the inside of cells in a vitrified state. It can also be seen that the vitrified state is more stably formed by including sugars, which are the cleavage products of hyaluronic acid. It is considered that vitrification occurs stably and efficiently because the formation of ice crystals around the cells is suppressed by sugars with low molecular weight.

[0182] <Test Example 8: Evaluation of intracellular vitrification state using brightness difference> Cultured primary canine mesenchymal stem cells (cyagen C160) were added at 1 × 10 6The cells were suspended in the test sample solutions (serum-free) of Examples 1 to 5 and Comparative Examples 1 to 10 at a concentration of 10 / mL. As a control, a control suspension was prepared in the test sample solution of Comparative Example 2 consisting of α-MEM medium without a cryopreservative. Then, 5 μL of the cell suspension and the control suspension containing each test sample solution were added to a hard glass sample placement plate (16φ×0.12 mm), covered with a hard glass cover glass (12φ×0.12 mm), cooled to −80° C. at 5° C. / min on a linKam microscope cooling stage (THMS600), and images of the solidified bodies were taken at −80° C. with a transmitted light microscope (Olympus BX53). The results of Example 1 and Comparative Examples 1 and 2 are shown in FIGS. 8A and 8B.

[0183] The difference (absolute value) in brightness between the inside and outside of the cell in the observation image shown in Figure 8A was analyzed using the image analysis software ImageJ. In each image, the brightness of the solvent region, the brightness of the inside of the cell, and the Munsell brightness were read under the same conditions, and the read data of the brightness of the solvent region and the brightness of the inside of the cell were compared with the read data of each Munsell brightness, and the Munsell brightness of the closest read data was adopted as the brightness of the solvent region and the brightness of the inside of the cell, and the brightness of the solvent and the brightness of the inside of the cell were quantified (Munsell valued). Note that if the read value of the brightness of the intracellular region or solvent region read by the image analysis software is darker than the read value of the darkest Munsell brightness value 0, the Munsell value of the intracellular region or solvent region is set to 0 for convenience, and if the read value of the brightness of the intracellular region or solvent region read by the image analysis software is brighter than the read value of the brightest Munsell brightness value 10, the Munsell brightness of the intracellular region or solvent region is set to 10 for convenience.

[0184] As a result of the measurement, in the control suspension (Comparative Example 2), the Munsell value of the solvent region was 5, the Munsell value of the intracellular region was 0, and the Munsell value difference between the solvent region and the intracellular region was 5. In Comparative Example 1, the value of the solvent region was 4, the Munsell value of the intracellular region was 0, and the Munsell value difference was 4. In contrast, in Example 1, the Munsell value of the solvent region was 4, the Munsell value of the intracellular region was 2, and the Munsell value difference was 2 (FIG. 8B). Similarly, for Examples 2 to 4 and Comparative Examples 3 to 10, the Munsell value of the solvent region and the Munsell value of the intracellular region were obtained, and the value difference was calculated. The results are shown in Table 1.

[0185] When ice crystals are formed during freezing, visible light is blocked and the brightness decreases. Therefore, it is preferable that the Munsell brightness is 2 or more in the solvent matrix region and the region inside the biological sample (intracellular region). A Munsell brightness of this order of magnitude indicates that ice crystals are not formed in the solvent matrix region and the region inside the biological sample (intracellular region), that is, the region is well vitrified. In Example 1, the Munsell brightness of the solvent region was 4 and the Munsell value of the intracellular region was 2, indicating that ice crystals were not formed in either region.

[0186] In addition, the difference in brightness between the Munsell brightness of the solvent region and the Munsell value of the intracellular region was 2 in Examples 2 to 5, as in Example 1. In the solidified body of the present invention, the solvent region in the solidified body is in a state in which ice crystals cannot form by adjusting the water-soluble polymer as described above. Therefore, the result that there is almost no difference in brightness between the solvent matrix side and the inside of the biological sample means that the frozen state is almost the same in the matrix region and the intracellular region. In other words, it shows that ice crystals are not formed in the region inside the biological sample in the solidified body of the present invention.

[0187] Furthermore, by comparing Examples 1 and 2 with Comparative Example 5, which does not contain hyaluronic acid having a viscosity average molecular weight of 1000 or less, and Comparative Example 10, which contains hyaluronic acid having a viscosity average molecular weight of 2000 or less, and by comparing Examples 3 and 4 with Comparative Example 9, which does not contain hyaluronic acid having a viscosity average molecular weight of 1000 or less, it was found that the difference in brightness between the solvent matrix region and the region inside the biological sample can also be adjusted by adding a sugar or its salt having a lower molecular weight than the water-soluble polymer to the aqueous polymer solution containing the water-soluble polymer or its salt. From Table 1, it can be seen that the brightness difference and the cell viability show a good correlation. The brightness difference between the intracellular region and the solvent region is preferably 3 or less. In addition, it is preferable that the brightness value of the solvent region is larger or the same as that of the intracellular region. Therefore, in the solidified body of the present invention, the difference in brightness between the solvent matrix region and the region inside the biological sample is adjusted to 3 or less by adding a low molecular weight sugar or its salt, thereby realizing a good vitrification state in both the intracellular region and the solvent region.

[0188] <Test Example 9: Evaluation of cells in solidified bodies> Cultured primary canine mesenchymal stem cells (cyagen C160) were added at 1 × 10 6The cells were suspended in the test sample solutions (serum-free) of Examples 1 to 5, Comparative Examples 1 to 10, and Production Examples 1 to 3 at a concentration of 10 cells / mL. Then, 5 μL of the cell suspension containing each test sample solution was added to a hard glass sample placement plate (16φ×0.12 mm), covered with a hard glass cover glass (12φ×0.12 mm), cooled to -80°C at 5°C / min on a linKam microscope cooling stage (THMS600) to solidify, and the solidified body was observed with a transmitted light microscope (Olympus BX53). Images of the solidified body in the culture medium (culture medium), i.e., before solidification and after cooling to -80°C (solidified state), were taken from above in the normal direction of the cooling stage. The cell area of ​​each cell was calculated using the image analysis software ImageJ (orthogonal projection area of ​​the cell) in the images taken before and after cooling, and the change in the orthogonal projection area of ​​the cell due to solidification was determined. The ratio of the cell area after solidification to the cell area in the culture medium (in the medium) before solidification was calculated and defined as the cell shrinkage rate (%). The results are shown in Table 1.

[0189] The cells frozen in the solidified bodies of Examples 1 to 5 showed cell shrinkage rates of 38, 33, 33, 33, and 40%, respectively. In the cryopreservation in the solidified bodies of Examples 1 to 5, the discharge of water from the cells to be frozen is promoted, and the inside of the cells is well dehydrated during freezing. In the freezing of the biological samples of Examples 1 to 5, in all cases, the water-soluble polymer and / or low molecular weight sugars are present in sufficient proximity to the periphery of the cells, and the water molecules that move from inside the cells to outside the cells due to the osmotic pressure difference between the intracellular fluid and the polymer solution are trapped in the matrix of the water-soluble polymer, further promoting the discharge of water from inside the cells, and the increased concentration of proteins and sugars in the cells makes the water in the cells supercooled, and further promoting the movement of water molecules through the cell membrane to the outside of the cells due to the vapor pressure difference between the supercooled water, thereby preventing or suppressing freezing in the cells and the growth of ice crystals. In addition, since the cells are shrinking, it can be seen that the water-soluble polymers and the like do not penetrate into the cells.

[0190] In contrast, in Comparative Example 1, in which DMSO was used as the test sample, and Comparative Example 2, in which only the medium was used, the orthogonal projection area of ​​the cells increased after freezing. In addition, in the test sample solutions of Comparative Examples 3, 4, and 6, in which the intrinsic viscosity (η) was outside the range of 0.20 dL / g or more and 0.95 dL / g or less, the cells had almost the same orthogonal projection area as before freezing. It is considered that dehydration within the cells did not occur sufficiently. On the other hand, in the test sample solutions (Comparative Examples 5, 9, and 10) in which the endothermic peak temperature of the DSC curve was outside the endothermic peak temperature of water, 0.7°C, and was below -1.4°C and above 1.1°C, the cells contracted, but not sufficiently. It is considered that dehydration of the cells was not sufficiently promoted. Therefore, it is considered that the survival rate of the cells after cryopreservation in the solidified bodies of these Comparative Examples was lower than that of Examples 1 to 5 in which the cells were well dehydrated. In Comparative Examples 7 and 8, the orthogonal projection area of ​​the cells increased from before freezing. In Comparative Example 8, it was observed that the cells burst due to freezing. In Comparative Examples 7 and 8, the water-soluble polymer is considered to have penetrated into the cells. Furthermore, the cell viability of the cells after cryopreservation in Comparative Examples 7 and 8 was also low. Such cell-permeable water-soluble polymers expand the cells when frozen and cause damage to the cells, and therefore are considered to be unsuitable as water-soluble polymers for polymer aqueous solutions used for cryopreservation of biological samples. Furthermore, in Production Examples 1 to 3, which have a small intrinsic viscosity (η), no change was observed in the orthogonal projection area of ​​the cells, and it was presumed that dehydration of the cells did not occur.

[0191] In the cryopreservation in the solidified body of the present invention, the inside of the cells is effectively dehydrated during freezing, so that damage to the cells during freezing is significantly reduced, and it is believed that this results in a high survival rate of the thawed cells.

[0192] <Test Example 10: Evaluation of cryoprotection for various cells> Cultured mouse-derived macrophage-like cell line (RAW264), human colon carcinoma-derived cells (Caco-2), and primary human pulmonary microvascular endothelial cells (HMVEC) were each cultured at 1 × 10 6The cells were suspended in the test sample solutions (serum-free) of Example 1 and Comparative Example 1 at a concentration of 10 ...

[0193] 9, when all cells were cryopreserved in the solidified material of the present invention, a high cell viability was obtained that was almost equal to or higher than that of Comparative Example 1 in which DMSO was used as the test sample. From this result, it was confirmed that in the solidified material of the present invention, various types of cells can be cryopreserved with high cell viability, regardless of whether they are primary cells or established cells, and regardless of the origin of the cells.

[0194] <Test Example 11: Evaluation of the effect of low molecular weight sugars on cell viability> Cultured primary canine mesenchymal stem cells (cyagen C160) were added at 1 × 10 6 The cells were suspended in each test sample solution (serum-free) of Production Examples 1 to 3 at a concentration of 10 ...

[0195] As shown in Table 1, the intrinsic viscosity (η) of low molecular weight saccharides or their salts (viscosity average molecular weights of 1000, 2000, and 3000, respectively) that are smaller than the molecular weight of the water-soluble polymer are 0.08, 0.14, and 0.19, respectively, which are outside the desired range of 0.2 dL / g or more and 0.95 dL / g or less. This Test Example 11 has revealed that such low molecular weight saccharides or their salts alone cannot achieve cell survival effects. In Production Example 3, a cell survival rate of about 10% was observed, which is presumably due to the hyaluronic acid with a molecular weight larger than 3000 that may be contained in the test sample of Production Example 3.

[0196] <Test Example 12: HPLC analysis of subcritically treated hyaluronic acid samples> A 1 wt% aqueous solution of the test samples of Production Examples 1 to 3 was prepared and filtered through a 0.45 μm membrane filter (Millipore), and the components of each test sample were analyzed by HPLC. As the mobile phase, a 16 mM NaH2PO4 aqueous solution was used as solution A, and an 800 mM NaH2PO4 aqueous solution was used as solution B. The components were separated using a ZORBAX NH2 (Agilent Technologies, Inc., column size φ4.6×250 mm, particle size 5 μm) normal phase HPLC column at a flow rate of 1.0 mL / min, a column temperature of 40° C., and a detection wavelength of 210 nm. The gradient conditions were mobile phase B concentration 0% (0 min) → mobile phase B concentration 100% (60 min). The results are shown in Figures 11A to C. In addition, as standards, aqueous solutions containing 0.2 wt% of hyaluronic acid oligosaccharides, HA02 (disaccharide), HA04 (tetrasaccharide), HA06 (hexasaccharide), HA08 (octasaccharide), and HA10 (decasaccharide) (all manufactured by Iduron) were prepared and analyzed by HPLC in the same manner. The results are shown in Figure 11D.

[0197] Under these HPLC analysis conditions, monosaccharides are observed at a retention time of 3.5 minutes, and disaccharides are observed at a retention time of around 9 minutes, as shown in Figure 11D. Figure 11A shows the analysis results of a test sample containing the hyaluronic acid cleavage product of Production Example 1 and having a viscosity average molecular weight of 1000, and a peak corresponding to monosaccharides is observed at a retention time of around 3.5 minutes, and a peak corresponding to disaccharides is observed at a retention time of around 9 minutes. In other words, the test sample of Production Example 1 contains such monosaccharide and disaccharide components, which are thought to contribute to the effect of improving cell viability.

[0198] <Test Example 13: HPLC analysis of the test sample of Example 1> The test sample of Example 1 (a hyaluronic acid sample having a viscosity average molecular weight of about 10,000 obtained by subcritical processing) was subjected to HPLC analysis under the same conditions as those for the HPLC analysis of the test samples of the above-mentioned Production Examples 1 to 3. The results are shown in FIG.

[0199] Similarly, when compared with Fig. 11D, peaks corresponding to monosaccharides and disaccharides are observed at retention times of about 3.5 minutes and about 9 minutes in the test sample of Example 1. In other words, the test sample of Example 1 also contains such monosaccharide and disaccharide components, which is considered to be the reason for the high cell viability effect.

[0200] From the above results, it can be seen that in the solidified body of the present invention, the inside of the biological sample is stably vitrified like the matrix portion, and thus the growth of ice crystals in the biological sample during freezing is prevented or suppressed. It can be seen that the solidified body of the present invention has a remarkable effect of being able to freeze and preserve biological samples with high cell survival rate, basically without requiring the addition of cell-permeable and cytotoxic compounds such as DMSO and ethylene glycol, and / or serum or serum-derived proteins. In the solidified body of the present invention, cells are well protected and their properties are maintained.

[0201] It is possible to add proteins that are free of bacterial or viral contamination, and it is also possible to use compounds that are cell-permeable and toxic at low concentrations that do not impair cell function.

Claims

1. A solidified body comprising a matrix containing an aqueous solvent and a water-soluble polymer or a salt thereof, and a biological sample, The biological sample has an orthogonal projection area smaller than 1 and reduced to 1 / 3.5 or more compared to that before solidification, a difference between a lightness in the Munsell color system of a region occupied by the biological sample and a lightness in the Munsell color system of a region occupied by the matrix is ​​3 or less when viewed from a light exit side when visible light is transmitted through the region; A solidified body characterized in that in a DSC curve of the matrix during a temperature rise process obtained using a differential scanning calorimeter (DSC) under the measurement conditions of the following (1) to (2), no endothermic peak is observed, or the temperature at which an endothermic peak is observed is higher than -1.4°C and 1.1°C or lower. (DSC measurement conditions) (1) After holding at 20°C for 1 minute, the temperature was decreased to -80°C at a rate of 5°C / min. (2) After holding at -80°C for 1 minute, the temperature was increased to 20°C at a rate of 10°C / min.

2. 2. The solidified product according to claim 1, which is a solid frozen product.

3. 3. The solidified body according to claim 1, wherein the water-soluble polymer or its salt is contained in an amount of 0.1 to 20 w / v %.

4. The solidified body according to any one of claims 1 to 3, wherein in a DSC curve during a temperature rise obtained under the measurement conditions of (1) to (2), the endothermic amount of an endothermic peak during the temperature rise is 0 J / g or 65% or less of the corresponding endothermic amount of a reference liquid consisting of water.

5. 5. The solidified body according to claim 1, wherein the biological sample is a cell, and the cell is a mammalian cell.

6. 6. The solidified body according to claim 5, wherein the biological sample is a cell, and the cell is a mammalian mesenchymal stem cell, a mammalian blood cell, or a mammalian endothelial cell.

7. The solidified form according to any one of claims 1 to 6, which is melted and used as a solution for administering a biological sample.

8. The solidified body of claim 7, wherein the amount of HGF produced by the biological sample contained in the biological sample administration solution is suppressed compared to the amount of HGF produced by the biological sample in the solidified body containing DMSO instead of the water-soluble polymer or its salt after melting.

9. The solidified body according to claim 7, wherein the amount of IL-10 produced by the biological sample contained in the biological sample administration solution is increased as compared with the amount of IL-10 produced by the biological sample in the solidified body containing DMSO instead of the water-soluble polymer or its salt after thawing.

10. A method for producing a solidified body containing a biological sample, comprising the steps of: A water-soluble polymer or a salt thereof is dissolved in an aqueous solvent. When frozen at −80° C., the biological sample has an orthogonal projection area that is smaller than 1 and is reduced to 1 / 3.5 or more compared to that before solidification, when frozen at −80° C., a difference between the lightness in the Munsell color system of a region occupied by the biological sample and the lightness in the Munsell color system of a region other than the region occupied by the biological sample is 3 or less when viewed from the light exit side when visible light is transmitted through the biological sample, A step of preparing an aqueous polymer solution, which has been adjusted so that, in a DSC curve during a temperature rise obtained under the following measurement conditions (1) to (2) using a differential scanning calorimeter (DSC), no endothermic peak is observed or the temperature at which an endothermic peak is observed is greater than −1.4° C. and equal to or less than 1.1° C.; A step of immersing the biological sample in the aqueous polymer solution; and a step of cooling and freezing the aqueous polymer solution containing the biological sample. (DSC measurement conditions) (1) After holding at 20°C for 1 minute, the temperature was decreased to -80°C at a rate of 5°C / min. (2) After holding at -80°C for 1 minute, the temperature was increased to 20°C at a rate of 10°C / min.

11. The method for producing a solidified body according to claim 10, wherein the step of cooling and freezing the aqueous polymer solution containing the biological sample is carried out by cooling and freezing the aqueous polymer solution to a temperature of -27°C or lower by a slow freezing method at a cooling rate of 10°C / min or less.

12. The method for producing a solidified body according to claim 10 or 11, wherein the solidified body contains the water-soluble polymer in an amount of 0.1 to 20 w / v % or less.

13. The method for producing a solidified body according to any one of claims 10 to 12, wherein in a DSC curve during a temperature rise obtained under the measurement conditions of (1) to (2), the endothermic amount of an endothermic peak during the temperature rise is 0 J / g or 65% or less of the corresponding endothermic amount of a reference solution consisting of water.

Citation Information

Patent Citations

  • Method of engrafting cells from parenchymal tissues

    JP2017131682A

  • Compositions and Methods for Reducing Ice Crystal Formation

    JP2018538359A

  • Vitrification stabilizer for animal cell cryopreservation fluid

    WO2017141991A1

  • Cryoprotectant and / or cryopreservant composition, methods and uses thereof

    WO2018211454A2

  • Serum-free medium for freeze stocking

    JP1988216476A